Bonded body, bonded body dispensing method, and thermosetting

By adding a thermal polymerization initiator, polymer and multifunctional monomer to the thermosetting adhesive, the problem of unstable peelability of the thermosetting adhesive in the prior art is solved, and the high-temperature heating is achieved in a short time The effect of effectively disengaging the bonding state.

CN119486873APending Publication Date: 2025-02-18NITTO DENKO CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202380051377.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-28
Filing Date
2023-07-26
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing thermosetting adhesives are difficult to maintain stable peelability when heated at high temperatures, resulting in natural peeling or increased peeling force of the adhesive, making it difficult to be suitable for scenarios where manpower is required to release the bonding state.

Method used

A thermosetting adhesive containing a thermal polymerization initiator, a polymer and a multifunctional monomer was developed. The peel strength of the glass plate after heating at 180°C for 30 minutes is 1.0N/20mm or less, and has easy heating. Peelability.

Benefits of technology

By heating at a short time at high temperature, the bonding state of the joint can be effectively removed, and the peeling force is maintained within a predetermined range when heating continuously, avoiding the problem of natural peeling of the adhesive or the peeling force rise.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119486873A_ABST
    Figure CN119486873A_ABST
Patent Text Reader

Abstract

Provided is a bonded body that can be disassembled even if deformation of an adherend cannot be used for peeling, such as a bonded body in which rigid bodies are bonded to each other by an adhesive. Provided is a joined body provided with a first member, a second member, and a joining part which is disposed between the first member and the second member and joins the first member and the second member. In the bonded body, the bonding part contains a thermosetting adhesive. In addition, the peel strength of the thermosetting adhesive with respect to a glass plate after heating at 180 DEG C for 30 minutes is 1.0 N / 20 mm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a joined body, a method for disassembling a joined body, and a thermosetting adhesive for the joined body.

[0002] This application claims priority based on Japanese Patent Application No. 2022-120903 filed on July 28, 2022, the entire contents of which are incorporated herein by reference. Background Art

[0003] Generally, adhesives (also called pressure-sensitive adhesives. The same applies hereinafter) have the following properties: they are in a soft solid (viscoelastic) state in a temperature range near room temperature, and are easily adhered to an adherend by pressure. In view of the excellent operability of pasting to an adherend, adhesives are widely used in various fields in the form of an adhesive sheet with an adhesive layer on a support, or in the form of an adhesive sheet without a support. Among such adhesives, there are adhesives that are used by adhering to an adherend and are removed from the adherend after the purpose of the bonding is completed. As prior art documents disclosing such prior art, Patent Documents 1 to 4 can be cited. Patent Documents 1 to 4 disclose thermosetting adhesives.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-29105

[0007] Patent Document 2: Japanese Patent Application Publication No. 2016-204617

[0008] Patent Document 3: Japanese Patent Application Publication No. 2019-56101

[0009] Patent Document 4: Japanese Patent Application Publication No. 10-209087

[0010] Non-patent literature

[0011] Non-patent literature 1: Simone Napolitano, 'Irreversible adsorption of polymer melts and nanoconfinement effects', SoftMatter, 2020, 16, pp. 5348-5365

[0012] Non-Patent Document 2: Ben O'Shaughnessy and Dimitrios Vavylonis, 'Non-Equilibrium in Adsorbed Polymer Layers', J. Phys.: Condens. Matter, 17, 2005, pp. R63-99 Summary of the invention

[0013] Problems to be solved by the invention

[0014] For adhesives used for peeling and removing from adherends, it is required to have good adhesion during bonding to adherends and to be easily peeled from adherends after the bonding purpose is completed. As adhesives with such performance, adhesives that have a certain adhesive force when bonding and fixing and can reduce the peeling force when peeling and removing can be used. As the above-mentioned adhesives that can reduce the peeling force, it is known that there are ultraviolet irradiation peeling type adhesives that reduce the peeling force by irradiating ultraviolet rays, and electrical peeling type adhesives that reduce the peeling force by applying voltage to the adherend. However, for example, ultraviolet irradiation peeling type adhesives cannot be applied to adherends that are not transparent to light, and electrical peeling type adhesives cannot be applied to adherends with low conductivity such as resin materials, and so on, there are restrictions on the materials of the adherends.

[0015] In addition, as an adhesive that is easily peelable by heating, there is a known technique in which a foaming agent or heat-expandable microspheres are contained in the adhesive and the adhesive is foamed or expanded by heating at a predetermined temperature to be peeled. However, the above-mentioned heat-easy peelable adhesive will peel naturally by heating, so there is a case where the adhesive is unexpectedly separated from the adherend due to the arrangement of the adherend after heating, the application of vibration, and other treatment methods.

[0016] In addition, the thermosetting adhesives described in Patent Documents 1 to 4 cannot have stable heat-resistance. For example, when an adherend such as glass or metal is heated at a high temperature while being attached with an adhesive, the adhesive will usually adsorb to the surface of the adherend, thereby increasing the peeling force (heavy peeling). It is difficult for the above-mentioned thermosetting adhesives to make the curing of the adhesive during high-temperature heating appear before the adsorption of the adhesive to the adherend, and therefore, it is believed that the reduction in peeling force and the suppression of peeling force increase based on the curing of the adhesive will not be obtained. Regarding this point, as a reference, Non-Patent Documents 1 to 2 describe various polymers that have adsorption force when heated.

[0017] On the other hand, the inventor of the present application has conducted research and development of thermosetting adhesives based on a design concept different from the past, and successfully obtained an adhesive with easy peeling (heat-peelable) that reduces the peeling force by being attached to the adherend and heated at a high temperature of more than 150°C. If the above-mentioned heat-peelable property is utilized, the peeling is easy by heating at a specified temperature, and people can easily release the bonding state of the adherend with a specified heat resistance by hand without causing damage to the adherend or with less physical load. In particular, as an adhesive that joins rigid bodies to each other, even if the bonding force to the adherend is set to be low, it is still necessary to release the bonding state of the entire bonding surface because it is impossible to deform the rigid adherend for the peeling of the adhesive, etc., and sometimes it is difficult to use manpower to release the bonding of the adherend. For such a joint body, if the above-mentioned adhesive with heat-peelable property (heat-peelable adhesive) can be applied to easily disassemble the joint body, it can be used in scenes where it is difficult to apply the previous peeling force reduction means, so it is useful.

[0018] Therefore, the object of the present invention is to provide a bonded body that can be disassembled by using a heat-peelable thermosetting adhesive even when the bonded body is formed by bonding rigid bodies to each other with an adhesive and the deformation of the adherend cannot be used for peeling. Another related object of the present invention is to provide a thermosetting adhesive for the above bonded body. Another related object of the present invention is to provide a method for disassembling the above bonded body.

[0019] Means for solving problems

[0020] According to the present specification, a joint body is provided, which comprises a first member, a second member and a joint portion, the joint portion being arranged between the first member and the second member and joining the first member and the second member. In the joint body, the joint portion comprises a thermosetting adhesive. Moreover, the peel strength of the thermosetting adhesive after heating to a glass plate measured after heating at 180°C for 30 minutes is 1.0N / 20mm or less. With respect to the joint body of the above-mentioned structure, since a thermosetting adhesive having a peel strength of 1.0N / 20mm or less after heating to a glass plate after heating at 180°C for 30 minutes is used in the joint portion for joining the first member and the second member, it is possible to join the first member and the second member well, and when it is desired to release the joining state, even if the first member and the second member are both rigid bodies and the deformation of the adherend cannot be used for peeling, they can be disassembled by short-time high-temperature heating. Heat peeling using the heat-peelable adhesive is useful as a means for disassembling a bonded body in situations where conventional peeling force reducing means such as ultraviolet irradiation peelable adhesives and electropeelable adhesives are difficult to apply.

[0021] In some embodiments, the first component and the second component are both rigid bodies. In the case of a joint body in which both the first and second components are rigid bodies, operations such as deforming the adherend cannot be used to release the joint state, and considerable force is required to release the entire bonding state of the bonding surface. In this regard, by using an adhesive that is easily peelable by heating, it can be disassembled by short-term high-temperature heating. The materials of the first and second components may be the same or different. As materials that can be used as rigid bodies for the first and second components, materials composed of glass, metal materials or ceramic materials can be cited.

[0022] In some embodiments, the post-heat peel strength of the thermosetting adhesive on the glass plate measured after heating at 180°C for 1 hour is 1.0N / 20mm or less. The adhesive satisfying the above characteristics is cured by short-term high-temperature heating, and the peeling force on the adherend is reduced. Furthermore, even if the heating is continued thereafter, the peeling force of the adhesive on the adherend does not increase, but is maintained within a specified range. Therefore, even if it is used in a continuously heated manner, the bonded body can be disassembled.

[0023] In the technology disclosed herein, in the joint portion for joining the first member and the second member, a substrate-free adhesive sheet formed only by an adhesive layer (in the joint body, an adhesive or a layer (adhesive layer) formed by an adhesive) can be used, and a double-sided adhesive sheet with a substrate (in the joint body, a laminated structure of the first adhesive layer, the substrate layer and the second adhesive layer) can also be used. In some embodiments, the above-mentioned joint portion can be formed by the above-mentioned thermosetting adhesive.

[0024] In some embodiments, the thermosetting adhesive contains a thermal polymerization initiator. When the adhesive contains the thermal polymerization initiator, the thermal polymerization initiator reacts when heated, and the adhesive is thermally cured. Thus, easy peelability by heating can be achieved ideally.

[0025] In some embodiments, the thermosetting adhesive comprises a polymer and a multifunctional monomer. The technology disclosed herein can be ideally implemented using a thermosetting adhesive comprising a polymer and a multifunctional monomer. As the polymer, for example, an acrylic polymer is preferably used.

[0026] In addition, according to the present specification, a thermosetting adhesive for use in any of the joints disclosed herein is provided. The post-heating peel strength of the thermosetting adhesive on a glass plate measured after heating at 180°C for 30 minutes is less than 1.0N / 20mm. By using a thermosetting adhesive that meets the above characteristics for the component joints of the joint, good bonding can be achieved, and the joint can be disassembled by short-term high-temperature heating. For example, even in the case where the adherends are all rigid bodies and deformation of the adherends cannot be used for peeling, the joint can be disassembled by short-term high-temperature heating.

[0027] In addition, according to this specification, a method for disassembling a joint body of any one of the disclosed herein is provided. The method includes: subjecting the above-mentioned joint body to a heat treatment at a temperature higher than 150°C to separate the first component from the second component. The adhesive used in the technology disclosed herein is a heat-strippable thermosetting adhesive, so the bonding state of the first component and the second component can be easily released by performing a heat treatment exceeding 150°C. For example, even in the case where the first component and the second component are both rigid bodies and the deformation of the adherend cannot be used for peeling, the joint body can be disassembled by short-term high-temperature heating. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] [ Figure 1 ] is a cross-sectional view schematically showing the structure of an adhesive sheet involved in one embodiment.

[0029] [ Figure 2 ] is a cross-sectional view schematically showing the structure of a bonding body involved in one embodiment. DETAILED DESCRIPTION

[0030] The following describes a suitable embodiment of the present invention. Matters necessary for implementing the present invention other than those specifically mentioned in this specification can be understood by those skilled in the art based on the teachings on the implementation of the invention recorded in this specification and the technical common sense at the time of filing the application. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in the field.

[0031] It should be noted that, in the following drawings, the same reference numerals are sometimes used to mark components and parts that play the same role for description, and repeated descriptions are sometimes omitted or simplified. In addition, the embodiments described in the drawings are illustrated for the purpose of clearly describing the present invention, and do not necessarily accurately represent the size or reduction ratio of the product actually provided.

[0032] In this specification, the so-called "base polymer" of the adhesive refers to the main component of the rubber polymer contained in the adhesive. The so-called rubber polymer refers to a polymer that exhibits rubber elasticity in a temperature range near room temperature. In addition, in this specification, the so-called "main component" refers to a component contained in an amount exceeding 50% by weight unless otherwise specified.

[0033] In this specification, the term "acrylic polymer" refers to a polymer containing monomer units derived from a monomer having at least one (meth)acryloyl group in one molecule as monomer units constituting the polymer. The acrylic polymer in this specification is defined as a polymer containing monomer units derived from an acrylic monomer.

[0034] In addition, in this specification, the so-called "acrylic monomer" refers to a monomer having at least one (meth)acryloyl group in one molecule. Here, the so-called "(meth)acryloyl group" refers to both acryloyl and methacryloyl groups. Therefore, the concept of acrylic monomers mentioned here may include both monomers having an acryloyl group (acrylic monomer) and monomers having a methacryloyl group (methacrylic monomer). Similarly, in this specification, respectively, the so-called "(meth)acrylic acid" refers to both acrylic acid and methacrylic acid, and the so-called "(meth)acrylate" refers to both acrylate and methacrylate. The same is true for other similar terms.

[0035] In addition, in this specification, "weight" can be replaced by "mass". For example, "weight %" can be replaced by "mass %", and "weight parts" can be replaced by "mass parts".

[0036] <Characteristics of thermosetting adhesives>

[0037] (Peel strength after heating F1)

[0038] The thermosetting adhesive disclosed herein has a peel strength F1 to a glass plate measured after heating at 180°C for 30 minutes (peel strength to a glass plate after 30 minutes of heating) of 1.0 N / 20 mm or less. The adhesive showing the peel strength F1 to a glass plate after 30 minutes of heating is easily peelable by heating, and is therefore heat cured by high-temperature heating for a short time, thereby being easily peelable, and can be easily peeled from the adherend, and can be released from the adherend without deforming the adherend, thereby releasing the bonded body. From the viewpoint of peelability and disassembly of the bonded body, it is appropriate that the peel strength F1 to a glass plate after 30 minutes of heating is 0.9 N / 20 mm or less, preferably 0.8 N / 20 mm or less, more preferably 0.6 N / 20 mm or less, further preferably 0.5 N / 20 mm or less, and can be 0.4 N / 20 mm or less, or can be 0.3 N / 20 mm or less. The lower limit of the peel strength F1 of the glass plate after 30 minutes of heating may be 0.0 N / 20 mm, or may be 0.01 N / 20 mm or more (for example, 0.1 N / 20 mm or more). Specifically, the peel strength F1 of the glass plate after 30 minutes of heating refers to the peel strength of the glass plate measured at a peeling angle of 180 degrees and a speed of 300 mm / min in an environment of 23° C. after the glass plate is attached to an adherend and subjected to a heating treatment at 180° C. for 30 minutes. The peel strength F1 of the glass plate after 30 minutes of heating is more specifically measured by the method described in the Examples described below.

[0039] (Peel strength after heating F2)

[0040] In some embodiments, the peel strength F2 of the thermosetting adhesive to the glass plate measured after heating at 180°C for 1 hour (peel strength to the glass plate after 1 hour heating) is preferably 1.0N / 20mm or less. The adhesive showing the above-mentioned peel strength F2 to the glass plate after 1 hour heating is cured by short-term high-temperature heating, and the peeling force to the adherend is reduced (heating easy peeling). Furthermore, even if it is continuously heated afterwards, the peeling force of the adhesive to the adherend will not increase, but will be maintained within a specified range. Therefore, even if it is used in a continuously heated manner, the peeling property from the adherend is good, and the disassembly of the joint body can be performed. From the viewpoint of peeling property and disassembly property of the joint body, it is appropriate that the above-mentioned peel strength F2 to the glass plate after 1 hour heating is less than 0.9N / 20mm, preferably less than 0.8N / 20mm, more preferably less than 0.6N / 20mm, further preferably less than 0.5N / 20mm, and can be less than 0.4N / 20mm, or less than 0.3N / 20mm. The lower limit of the peel strength F2 of the glass plate after heating for 1 hour may be 0.0 N / 20 mm, or may be 0.01 N / 20 mm or more (for example, 0.1 N / 20 mm or more). Specifically, the peel strength F2 of the glass plate after heating for 1 hour refers to the peel strength of the glass plate measured at a peeling angle of 180 degrees and a speed of 300 mm / min under an environment of 23° C. after heating at 180° C. for 1 hour in a state of being attached to an adherend. The peel strength F2 of the glass plate after heating for 1 hour is more specifically measured by the method described in the Examples described later.

[0041] (Initial peel strength F0)

[0042] Although not particularly limited, it is appropriate for the initial peel strength (initial peel strength to glass plate) F0 of the thermosetting adhesive to the glass plate to be 0.5N / 20mm or more, and may be 0.8N / 20mm or more, and preferably greater than 1.0N / 20mm. An adhesive showing the above-mentioned initial peel strength F0 to the glass plate can exhibit good adhesion to the adherend. From the viewpoint of adhesion, the above-mentioned initial peel strength F0 to the glass plate may be 1.2N / 20mm or more, 1.5N / 20mm or more, 1.8N / 20mm or more, or 2.0N / 20mm or more. The upper limit of the initial peel strength F0 to the glass plate can be appropriately set according to the required adhesion, and is therefore not limited to a specific range, and may be, for example, less than about 20N / 20mm, less than about 10N / 20mm, less than about 5N / 20mm, or less than about 3N / 20mm. The initial peel strength F0 against a glass plate is specifically measured at a peeling angle of 180 degrees and a speed of 300 mm / min at 23° C. The initial peel strength F0 against a glass plate is more specifically measured by the method described in the examples described below.

[0043] (F1 / F0)

[0044] In some embodiments, the peel strength F1 [N / 20mm] of the thermosetting adhesive after 30 minutes of heating is less than 100% of the initial peel strength F0. In other words, the ratio (F1 / F0) of the thermosetting adhesive is less than 1. The above ratio (F1 / F0) can be less than 0.8, and it is appropriate to be less than 0.5, preferably less than 0.4, more preferably less than 0.3, further preferably less than 0.2, and can also be less than 0.15. Thermosetting adhesives that meet this characteristic are well bonded to the adherend and can exhibit good heating and easy peeling properties when peeled off after a short-time heating treatment. The lower limit value of the above ratio (F1 / F0) is not particularly limited, for example, it can also be about 0.01 or more.

[0045] (F2 / F0)

[0046] In some embodiments, the peel strength F2 [N / 20mm] of the thermosetting adhesive after 1 hour of heating is less than 100% of the initial peel strength F0. In other words, the ratio (F2 / F0) of the thermosetting adhesive is less than 1. The above ratio (F2 / F0) can be less than 0.8, and it is appropriate to be less than 0.5, preferably less than 0.4, more preferably less than 0.3, further preferably less than 0.2, and can also be less than 0.15. Thermosetting adhesives that meet this characteristic are well bonded to the adherend, and even after continuous heating for a certain period of time, they can also exhibit good heating and easy peeling properties when peeled off. The lower limit value of the above ratio (F2 / F0) is not particularly limited, for example, it can also be about 0.01 or more.

[0047] (Peel strength after storage FS0)

[0048] Although not particularly limited, in some embodiments, for the thermosetting adhesive, the peel strength to the glass plate (peel strength to the glass plate after storage) FS0 measured using the thermosetting adhesive after storage at 60°C for 7 days is appropriately 0.5N / 20mm or more, and may be 0.8N / 20mm or more, and preferably greater than 1.0N / 20mm. For the thermosetting adhesive that exhibits the above-mentioned peel strength to the glass plate FS0 after storage, good adhesion can be exhibited after storage regardless of long-term storage, temperature conditions during storage, etc. From the perspective of adhesion, the above-mentioned peel strength to the glass plate FS0 after storage may be 1.2N / 20mm or more, 1.5N / 20mm or more, or 1.8N / 20mm or more. The upper limit of the peel strength to the glass plate FS0 after storage may be, for example, about 20N / 20mm or less, about 10N / 20mm or less, about 5N / 20mm or less, or about 3N / 20mm or less. The post-storage peel strength FS0 on a glass plate specifically refers to the peel strength of the thermosetting adhesive after storage at 60° C. for 7 days on a glass plate measured at 23° C. at a peeling angle of 180 degrees and a speed of 300 mm / min.

[0049] The above-mentioned glass plate peel strength FS0 after storage is more specifically measured by the following method.

[0050] The thermosetting adhesive (which may be in the form of an adhesive sheet) is stored at 60°C for 7 days. Using the thermosetting adhesive after storage, an evaluation sample is prepared by the method described in the determination of the initial peel strength F0. Then, the peel strength (peel strength to the glass plate after storage) FS0 [N / 20 mm width) is measured by the same method as the method described in the initial peel strength F0. The adherend, tensile testing machine, and other matters are the same as those for the determination of the initial peel strength F0.

[0051] (Peel strength after storage / heating FS1)

[0052] Although not particularly limited, in some embodiments, for thermosetting adhesives, it is appropriate that the peel strength to the glass plate measured after the thermosetting adhesive stored at 60°C for 7 days is affixed to a glass plate as an adherend and heated at 180°C for 1 hour (peel strength to the glass plate after storage / heating) FS1 is less than 3N / 20mm, and is preferably 1.0N / 20mm or less. Thermosetting adhesives showing the above-mentioned peel strength to the glass plate after storage / heating FS1 are easily peelable by heating even when stored for a long time or when the temperature conditions during storage change, and have good storage stability. From the viewpoint of peelability and disassembly of the bonded body, the above-mentioned peel strength to the glass plate after storage / heating FS1 is preferably 0.8N / 20mm or less, more preferably 0.6N / 20mm or less, further preferably 0.5N / 20mm or less, particularly preferably 0.4N / 20mm or less, and may also be 0.3N / 20mm or less. The lower limit of the peel strength FS1 of the glass plate after storage / heating may be 0.0 N / 20 mm, or may be 0.01 N / 20 mm or more (e.g., 0.1 N / 20 mm or more). Specifically, the peel strength FS1 of the glass plate after storage / heating refers to the peel strength of the glass plate measured at a peeling angle of 180 degrees and a speed of 300 mm / min after the thermosetting adhesive stored at 60° C. for 7 days is attached to the adherend glass plate and subjected to a heating treatment at 180° C. for 1 hour.

[0053] The above-mentioned glass plate peel strength FS1 after storage / heating is more specifically measured by the following method.

[0054] The thermosetting adhesive (which may be in the form of an adhesive sheet) is stored at 60°C for 7 days. Using the thermosetting adhesive after storage, an evaluation sample is prepared by the method described in the determination of the initial peel strength F0. The obtained evaluation sample is heat-treated in an oven at 180°C for 1 hour and allowed to stand for 30 minutes at room temperature and pressure. Then, the evaluation sample is placed in a tensile testing machine at 23°C and 50% RH, and the peel strength (peel strength on the glass plate after storage / heating) FS1 [N / 20mm width] when the thermosetting adhesive is peeled from the adherend at a peeling angle of 180 degrees and a speed of 300mm / min is measured. The adherend, tensile testing machine, and other matters are the same as the determination of the initial peel strength F0.

[0055] (FS1 / FS0)

[0056] In some embodiments, the storage / post-heating peel strength FS1 [N / 20mm] of the thermosetting adhesive is lower than 100% of the post-storage peel strength FS0. In other words, the ratio (FS1 / FS0) of the thermosetting adhesive is lower than 1. It is appropriate that the above (FS1 / FS0) is less than 0.5, preferably less than 0.4, more preferably less than 0.3, further preferably less than 0.2, and may also be less than 0.15. Thermosetting adhesives that meet this characteristic can be well bonded to the adherend even after storage, and can exhibit good heat-peelability when peeled off after heat treatment, so they have excellent storage stability. The lower limit of the above ratio (FS1 / FS0) is not particularly limited, for example, it may also be greater than about 0.01.

[0057] (Total amount of released gas when kept at 180℃ for 1 hour)

[0058] In some embodiments, the total amount of released gas of the thermosetting adhesive when kept at 180°C for 1 hour is preferably 1000 μg or less (also referred to as 1000 μg / g or less) per 1 g of adhesive. In thermosetting adhesives that meet this characteristic, the released gas is limited to a specified amount or less, so it is not easy to cause adverse conditions caused by the released gas (such as a decrease in the vacuum degree, etc.). From this point of view, in some preferred embodiments, the total amount of released gas of the thermosetting adhesive when kept at 180°C for 1 hour is 950 μg / g or less, more preferably 900 μg / g or less, further preferably 850 μg / g or less, particularly preferably 800 μg / g or less, and can be 750 μg / g or less, or 700 μg / g or less. The lower the lower limit of the total amount of released gas of the thermosetting adhesive when kept at 180°C for 1 hour, the more preferred it is, and it can be about 1 μg / g or more (for example, 10 μg / g or more or 100 μg / g or more).

[0059] The total amount of gas released when the thermosetting adhesive is kept at 180°C for 1 hour is measured by using a thermosetting adhesive or an adhesive sheet containing a thermosetting adhesive as a measurement sample and analyzing the released gas when kept at 180°C for 1 hour using a gas chromatography-mass spectrometry (GC / MS) method. 2 The specific measurement conditions are as follows.

[0060] (Analysis device)

[0061] Heating device: GERSTEL, TDU2

[0062] GC / MS: Agilent Technologies, 8890 / 5977B

[0063] (Measurement conditions)

[0064] TDU conditions (sample): 30℃(1min)→720℃ / min→180℃(60min)

[0065] TDU conditions (standard product): 30℃(1min)→720℃ / min→300℃(5min)

[0066] CIS conditions: -150℃(2.5min)→12℃ / sec→300℃(10min)

[0067] GC / MS conditions

[0068] Chromatographic column: HP-Ultra1( df=0.33μm)

[0069] Column temperature: 40℃(5min)→10℃ / min→100℃→20℃ / min→300℃(9min)

[0070] Column pressure: Constant flow mode (113kPa, Vac)

[0071] Column flow rate: 1mL / min (He)

[0072] Injection method: CIS, Split (20:1)

[0073] Detector: MS

[0074] Ion source temperature: 230°C

[0075] Ionization method: EI (70eV)

[0076] <Thermosetting adhesive>

[0077] (polymer)

[0078] In the technology disclosed herein, the type of thermosetting adhesive (hereinafter, sometimes referred to as "adhesive") is not particularly limited. The adhesive disclosed herein may include one or more polymers of various rubber-like polymers such as acrylic polymers, rubber polymers (such as natural rubber, synthetic rubber, mixtures thereof, etc.), polyester polymers, urethane polymers, polyether polymers, silicone polymers, polyamide polymers, fluorine polymers, etc. that can be used in the field of adhesives. The above polymers are used as base polymers in adhesives and can function as structural polymers of molding adhesives. From the viewpoints of adhesive performance, cost, etc., it is preferred to use an adhesive containing an acrylic polymer or a rubber polymer as a base polymer. Among them, an adhesive (acrylic adhesive) using an acrylic polymer with excellent heat resistance as a base polymer is preferred.

[0079] Hereinafter, the description will be mainly about acrylic pressure-sensitive adhesives and pressure-sensitive adhesive sheets having a pressure-sensitive adhesive layer composed of the pressure-sensitive adhesive, that is, having an acrylic pressure-sensitive adhesive layer, but the pressure-sensitive adhesive disclosed herein is not intended to be limited to acrylic pressure-sensitive adhesives.

[0080] (Acrylic polymer)

[0081] In some embodiments, as an acrylic polymer, an acrylic polymer in which more than 50% by weight of the monomer components constituting the polymer are acrylic monomers is used. It is appropriate that the proportion of acrylic monomers in the above-mentioned monomer components is 60% by weight or more, preferably 70% by weight or more, more preferably 80% by weight or more, further preferably 85% by weight or more, for example, it can be 90% by weight or more. The upper limit of the proportion of acrylic monomers in the monomer components constituting the acrylic polymer is 100% by weight. From the viewpoint of obtaining the effect of using non-acrylic monomers, the proportion of the above-mentioned acrylic monomers can be, for example, 98% by weight or less, 95% by weight or less, or 92% by weight or less. Acrylic monomers can be used alone or in combination of two or more.

[0082] In some embodiments, the monomer component includes an alkoxy-containing (meth)acrylate. According to the acrylic polymer containing an alkoxy-containing (meth)acrylate as a monomer component, for example, there is a tendency to easily obtain compatibility with other components (for example, a multifunctional monomer described later) that may be included in the adhesive. The alkoxy-containing (meth)acrylate can be used alone or in combination of two or more.

[0083] Examples of (meth)acrylates containing an alkoxy group include alkoxyalkyl (meth)acrylates such as methoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, propoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, and ethoxypropyl (meth)acrylate; alkoxy (poly)alkylene glycol (meth)acrylates such as methoxydiethylene glycol (meth)acrylate, methoxydipropylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, ethoxydipropylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypolypropylene glycol (meth)acrylate, ethoxypolyethylene glycol (meth)acrylate, and ethoxypolypropylene glycol (meth)acrylate; and the like. Among them, alkoxyalkyl (meth)acrylates are preferred, and among them, alkoxyalkyl (meth)acrylates having an alkoxy group having 1 to 4 carbon atoms (eg, 1, 2, or 3 carbon atoms) are more preferred, and methoxyethyl (meth)acrylate is particularly preferred.

[0084] The content of the (meth)acrylate containing alkoxy groups in the monomer components constituting the acrylic polymer is not particularly limited. From the viewpoint of effectively obtaining the effect brought about by the use of the (meth)acrylate containing alkoxy groups, the content of the (meth)acrylate containing alkoxy groups in the above-mentioned monomer components is usually about 1% by weight or more, for example, it can be 10% by weight or more, it can be 30% by weight or more, and it can also be 50% by weight or more. In some embodiments, from the viewpoint of adhesive properties such as adhesive strength and compatibility with other components (such as multifunctional monomers), the content of the (meth)acrylate containing alkoxy groups in the above-mentioned monomer components is, for example, more than 50% by weight, preferably 60% by weight or more, more preferably 70% by weight or more, and further preferably 80% by weight or more. The upper limit of the content of the alkoxy-containing (meth)acrylate in the above-mentioned monomer component is 100 weight % or less. For example, from the viewpoint of obtaining the effect of other copolymerizable monomers such as monomers containing functional groups, in some embodiments, the content of the alkoxy-containing (meth)acrylate is advantageously about 99 weight % or less, and can be 95 weight % or less, 93 weight % or less, or 90 weight % or less.

[0085] In some other embodiments, the monomer component constituting the acrylic polymer may be a component containing a linear alkyl (meth)acrylate having a linear or branched alkyl group with 1 to 20 carbon atoms at the ester terminal. Hereinafter, a linear alkyl (meth)acrylate having an alkyl group with X to Y carbon atoms at the ester terminal may be referred to as “C X-Y Alkyl (meth) acrylate". It should be noted that in the present specification, the term "chain" is used to include linear and branched chains. The above-mentioned chain alkyl (meth) acrylates can be used alone or in combination of two or more.

[0086] As C 1-20Specific non-limiting examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, Nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, and the like.

[0087] Among these, it is preferred to use at least C 4-20 Alkyl (meth) acrylate, more preferably at least C 4-18 In some embodiments, as C 1-20 Alkyl (meth) acrylate, preferably C 4-8 Among them, it is more preferred to use C 4-8 Alkyl acrylate. 4-8 The alkyl (meth)acrylate can be used alone or in combination of two or more. 4-8 The use of alkyl (meth) acrylates tends to easily obtain good adhesive properties (adhesive strength, etc.). For example, as the above-mentioned monomer component, an acrylic polymer containing one or both of n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA) is preferred, and an acrylic polymer containing at least 2EHA is particularly preferred. 1-20 In some other forms of alkyl (meth) acrylate, C 7-12 Alkyl (meth) acrylate. 7-12 The alkyl (meth)acrylate can be used alone or in combination of two or more. 7-12 Alkyl (meth) acrylate, preferably C 7-10 Alkyl acrylate, more preferably C 7-9 The alkyl acrylate is more preferably a C8 alkyl acrylate.

[0088] Among the monomer components constituting the acrylic polymer, 1-20The content of alkyl (meth) acrylate is not particularly limited. 1-20 From the viewpoint of the effect of using alkyl (meth)acrylate, C 1-20 The content of the alkyl (meth) acrylate is generally about 1% by weight or more, for example, 10% by weight or more, 30% by weight or more, or 50% by weight or more. In some embodiments, from the perspective of adhesive properties such as adhesive strength, the C 1-20 The content of the alkyl (meth)acrylate is, for example, more than 50% by weight, preferably 60% by weight or more, more preferably 70% by weight or more, and even more preferably 80% by weight or more. 1-20 The upper limit of the content of the alkyl (meth) acrylate is 100 wt % or less. For example, from the viewpoint of obtaining the effect of other copolymerizable monomers such as monomers containing functional groups, in some embodiments, the C 1-20 The content of alkyl (meth) acrylate is advantageously about 99 wt % or less, and may be 95 wt % or less, 93 wt % or less, or 90 wt % or less. 1-20 The content of alkyl (meth) acrylate can range from 1-20 The above C included in the alkyl (meth) acrylate 4-20 Alkyl (meth) acrylate, C 4-18 Alkyl (meth) acrylate, C 4-8 Alkyl (meth) acrylate, C 4-8 Alkyl acrylate, C 7-12 Alkyl (meth) acrylate, C 7-10 Alkyl acrylate, C 7-9 The range of each content of alkyl acrylate, C8 alkyl acrylate, BA, and 2EHA.

[0089] In some embodiments, the monomer components constituting the acrylic polymer preferably include other monomers other than the above-mentioned alkoxyalkyl (meth) acrylate and chain alkyl (meth) acrylate. Such other monomers may be monomers (copolymerizable monomers) that can be copolymerized with alkoxyalkyl (meth) acrylate and chain alkyl (meth) acrylate. As the above-mentioned other monomers, monomers having polar groups (e.g., carboxyl groups, hydroxyl groups, rings containing nitrogen atoms, etc.) may be preferably used. Monomers having polar groups may help introduce crosslinking points into acrylic polymers and improve the cohesive force of adhesives. Other monomers may be used alone or in combination of two or more.

[0090] Specific non-limiting examples of other monomers include the following monomers.

[0091] Monomers containing a carboxyl group: for example, acrylic acid, methacrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, and the like.

[0092] Monomers containing anhydride groups: for example, maleic anhydride, itaconic anhydride.

[0093] Monomers containing hydroxyl groups: for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate.

[0094] Monomers containing sulfonic acid groups or phosphoric acid groups: for example, styrene sulfonic acid, allyl sulfonic acid, sodium vinyl sulfonate, 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamidepropanesulfonic acid, (meth)acrylate sulfopropyl ester, (meth)acryloyloxynaphthalenesulfonic acid, 2-hydroxyethylacryloyl phosphate, etc.

[0095] Epoxy group-containing monomers: for example, epoxy group-containing acrylates such as glycidyl (meth)acrylate and 2-ethyl glycidyl (meth)acrylate ether, allyl glycidyl ether, and glycidyl (meth)acrylate ether.

[0096] Monomers containing cyano groups: for example, acrylonitrile, methacrylonitrile, etc.

[0097] Isocyanate group-containing monomer: for example, 2-isocyanateethyl (meth)acrylate, etc.

[0098] Amide-containing monomers: for example, (meth)acrylamide; N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, N,N-diisopropyl (meth)acrylamide, N,N-di (n-Butyl)N,N-dialkyl(meth)acrylamide, such as N-(meth)acrylamide, N,N-di(tert-butyl)(meth)acrylamide; N-monoalkyl(meth)acrylamide, such as N-ethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-butyl(meth)acrylamide, and N-n-butyl(meth)acrylamide; N-vinylcarboxylic acid amides, such as N-vinylacetamide; monomers having hydroxyl groups and amide groups, such as N-(2-hydroxyethyl)(meth)acrylamide, N-(2-hydroxypropyl)(meth)acrylamide, N-(1-hydroxypropyl)(meth)acrylamide, N-(3-hydroxypropyl)(meth)acrylamide N-hydroxyalkyl (meth) acrylamide, N-(2-hydroxybutyl) (meth) acrylamide, N-(3-hydroxybutyl) (meth) acrylamide, N-(4-hydroxybutyl) (meth) acrylamide and the like; monomers having an alkoxy group and an amide group, for example, N-alkoxyalkyl (meth) acrylamides such as N-methoxymethyl (meth) acrylamide, N-methoxyethyl (meth) acrylamide, N-butoxymethyl (meth) acrylamide; and N,N-dimethylaminopropyl (meth) acrylamide, N-(meth)acryloyl morpholine, alkoxy diacetone (meth) acrylamide, vinyl formamide, vinyl acetamide, and the like.

[0099] Monomers containing amino groups: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, tert-butylaminoethyl (meth)acrylate.

[0100] Monomers having an epoxy group: for example, glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, and allyl glycidyl ether.

[0101] Monomers having a ring containing a nitrogen atom: for example, N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisoxazole, N-vinylthiazole, N-vinylisothiazole, N-vinylpyridazine, etc. (for example, lactams such as N-vinyl-2-caprolactam).

[0102] Monomers having a succinimide skeleton include, for example, N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyhexamethylenesuccinimide.

[0103] Maleimides: for example, N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, N-phenylmaleimide, etc.

[0104] Itaconimides: for example, N-methyl itaconimide, N-ethyl itaconimide, N-butyl itaconimide, N-octyl itaconimide, N-2-ethylhexyl itaconimide, N-cyclohexyl itaconimide, N-lauryl itaconimide and the like.

[0105] Aminoalkyl (meth)acrylates: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, tert-butylaminoethyl (meth)acrylate.

[0106] Alkoxysilyl group-containing monomers: for example, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, and 3-(meth)acryloxypropylmethyldiethoxysilane.

[0107] Vinyl esters: for example, vinyl acetate, vinyl propionate, etc.

[0108] Vinyl ethers: For example, vinyl alkyl ethers such as methyl vinyl ether and ethyl vinyl ether.

[0109] Aromatic vinyl compounds: for example, styrene, α-methylstyrene, vinyltoluene, etc.

[0110] Olefins: for example, ethylene, butadiene, isoprene, isobutylene, etc.

[0111] (Meth)acrylates having an alicyclic hydrocarbon group: for example, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentyl (meth)acrylate, adamantyl (meth)acrylate, and the like.

[0112] (Meth)acrylates having an aromatic hydrocarbon group: for example, phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, and the like.

[0113] In addition, (meth)acrylates containing heterocycles such as tetrahydrofurfuryl (meth)acrylate, (meth)acrylates containing halogen atoms such as (meth)acrylates containing vinyl chloride and fluorine atoms, (meth)acrylates containing silicon atoms such as silicone (meth)acrylates, and (meth)acrylates obtained from terpene compound derivative alcohols, etc.

[0114] When using such other monomers, its usage amount is not particularly limited, and it is appropriate to be set as more than 0.01 weight % of the overall monomer component. From the viewpoint of better exerting the use effect of other monomers, the usage amount of other monomers can be set as more than 0.1 weight % of the overall monomer component, and can be set as more than 0.5 weight %. In addition, from the viewpoint of easily obtaining the balanced property of adhesive properties, it is appropriate to set the usage amount of other monomers as less than 50 weight % of the overall monomer component, and preferably be set as less than 40 weight %.

[0115] In some embodiments, the monomer components constituting the acrylic polymer may include a monomer having a nitrogen atom. By using a monomer having a nitrogen atom, the cohesive force of the adhesive is increased, and the adhesive force can preferably be increased. The monomer having a nitrogen atom can be used alone or in combination of two or more. As a suitable example of a monomer having a nitrogen atom, a monomer having a ring containing a nitrogen atom can be cited. As a monomer having a nitrogen atom and a monomer having a ring containing a nitrogen atom, the monomers exemplified above can be used, for example, N-vinyl cyclic amide represented by the general formula (1) can be used:

[0116] [Chemical formula 1]

[0117]

[0118] Here, in the general formula (1), R 1 is a divalent organic group, specifically -(CH2) n -. n is an integer of 2 to 7 (preferably 2, 3 or 4). Among them, N-vinyl-2-pyrrolidone (NVP) can be preferably used. Other suitable examples of monomers having nitrogen atoms include: N,N-dialkyl (meth)acrylamides such as (meth)acrylamide and N,N-dimethyl (meth)acrylamide; N-monoalkyl (meth)acrylamides such as N-isopropyl (meth)acrylamide; N-hydroxyalkyl (meth)acrylamides such as N-(2-hydroxyethyl)acrylamide (HEAA); N-acryloylmorpholine (ACMO); alkoxy diacetone (meth)acrylamide; vinyl formamide, vinyl acetamide; and the like. Among them, NVP, HEAA, and ACMO are more preferred.

[0119] The usage amount of the monomer with nitrogen atom (preferably the monomer with ring containing nitrogen atom) is not particularly limited, for example, it can be more than 1% by weight of the whole monomer component, or it can be more than 3% by weight. In some ways, the usage amount of the monomer with nitrogen atom in the above-mentioned monomer component is preferably more than 5% by weight, more preferably more than 7% by weight, and further preferably more than 9% by weight. In addition, it is appropriate to set the usage amount of the monomer with nitrogen atom to less than 40% by weight of the whole monomer component, which can be set to less than 35% by weight, can be set to less than 30% by weight, or can be set to less than 25% by weight. In some ways, the usage amount of the monomer with nitrogen atom can be set to less than 20% by weight of the whole monomer component, which can be set to less than 15% by weight, or can be set to less than 12% by weight.

[0120] In some embodiments, the monomer component may include a monomer containing a hydroxyl group. By using a monomer containing a hydroxyl group, the cohesion and crosslinking density of the adhesive can be adjusted, and the bonding strength can be improved. As a monomer containing a hydroxyl group, the monomers exemplified above can be used, for example, 2-hydroxyethyl acrylate (HEA) and 4-hydroxybutyl acrylate (4HBA) can be preferably used. The monomer containing a hydroxyl group can be used alone or in combination of two or more.

[0121] The amount used in the case of using a monomer containing a hydroxyl group is not particularly limited, for example, it can be more than 0.01% by weight of the entire monomer component, it can be more than 0.1% by weight, and it can also be more than 0.5% by weight. In some preferred embodiments, the amount of the monomer containing a hydroxyl group is more than 1% by weight of the entire monomer component, more preferably more than 2% by weight, and further preferably more than 3% by weight, for example, it can be more than 5% by weight. In addition, in some embodiments, it is appropriate to set the amount of the monomer containing a hydroxyl group to, for example, less than 40% by weight of the entire monomer component, preferably less than 30% by weight, more preferably less than 20% by weight, more preferably less than 10% by weight, and it can also be less than 7% by weight.

[0122] In some preferred embodiments, as monomer components of acrylic polymers, as monomers having polar groups (monomers containing polar groups), monomers having nitrogen atoms (e.g., monomers containing amide groups such as (meth)acrylamide, monomers containing rings containing nitrogen atoms such as NVP) and monomers containing hydroxyl groups (e.g., HEA, 4HBA) are used together. In this way, it is possible to achieve both adhesive force and cohesive force in a well-balanced manner. In the embodiment in which a monomer having nitrogen atoms and a monomer containing hydroxyl groups are used together, the amount of the monomer having nitrogen atoms is A N The amount of monomer containing hydroxyl group A OH Weight ratio (A N / A OH) is not particularly limited, and can be, for example, 0.1 or more, 0.5 or more, 1.0 or more, 1.2 or more, 1.5 or more, or 1.8 or more. N / A OH ) For example, it can be less than 10, less than 5, less than 3, or less than 2.5.

[0123] In some embodiments, the monomer component includes a monomer containing a carboxyl group. Suitable examples of monomers containing a carboxyl group include acrylic acid (AA) and methacrylic acid (MAA). Monomers containing a carboxyl group can be used alone or in combination of two or more. For example, AA and MAA can also be used in combination.

[0124] The usage amount of the monomer containing carboxyl can be, for example, more than 0.01 % by weight of the overall monomer component, can be more than 0.05 % by weight, can be more than 0.1 % by weight, can be more than 0.3 % by weight, and can also be more than 0.5 % by weight. The ratio of the above-mentioned monomer containing carboxyl can be, for example, less than 15 % by weight, can be less than 10 % by weight, can be less than 5 % by weight, can be less than 3 % by weight, can be less than 2 % by weight, and can also be less than 1 % by weight (for example, less than 1 % by weight).

[0125] In addition, when using an acrylic polymer with an ethylenically unsaturated group described later as a polymer, as other monomers, it is preferred to use a monomer with a functional group (functional group A) that can react with a functional group (functional group B) of a compound with an ethylenically unsaturated group described later. In this manner, the type of other monomers is determined according to the type of the above-mentioned compound. As other monomers with functional group A, for example, preferably a monomer containing a carboxyl group, a monomer containing an epoxy group, a monomer containing a hydroxyl group, a monomer containing an isocyanate group, and a monomer containing a hydroxyl group are particularly preferred. By using a monomer containing a hydroxyl group as other monomers, the acrylic polymer has a hydroxyl group. In contrast, as a compound with an ethylenically unsaturated group, for example, by using a monomer containing an isocyanate group, the hydroxyl group of the above-mentioned acrylic polymer reacts with the isocyanate group of the above-mentioned compound, and the ethylenically unsaturated group derived from the above-mentioned compound is introduced into the acrylic polymer.

[0126] In addition, when other monomers are used for the purpose of reacting with a compound having an ethylenically unsaturated group, from the viewpoint of adhesive properties such as thermosetting and cohesive force of the adhesive, it is appropriate that the amount of the other monomers (preferably monomers containing hydroxyl groups) is set to about 1 mol% or more of the total monomer components, preferably about 5 mol% or more, more preferably about 10 mol% or more, and further preferably about 15 mol% or more (for example, about 18 mol% or more). In addition, from the viewpoint of maintaining adhesive properties such as adhesive force well, it is appropriate that the amount of the other monomers is set to about 40 mol% or less of the total monomer components, preferably about 30 mol% or less, more preferably about 25 mol% or less, and for example, it can also be about 22 mol% or less.

[0127] In the acrylic polymer, as other monomer components, a multifunctional monomer having a polymerizable functional group (typically a free radical polymerizable functional group) having at least two (meth)acryloyl groups, vinyl groups, etc. with unsaturated double bonds can be included. As a monomer component, by using a multifunctional monomer, the cohesive force of the adhesive can be improved. The multifunctional monomer can be used as a crosslinking agent. As the multifunctional monomer, there is no particular limitation, for example, suitable substances among the substances exemplified as multifunctional monomers that can be included in the adhesive described later can be used alone or in combination of two or more.

[0128] The usage amount of the multifunctional monomer is not particularly limited, and can be appropriately set in a manner that achieves the purpose of use of the multifunctional monomer. The usage amount of the multifunctional monomer can be set to less than about 3 wt % of the above-mentioned monomer component, preferably less than about 2 wt %, more preferably less than about 1 wt % (e.g., less than about 0.5 wt %). The lower limit of the usage amount when using a multifunctional monomer is greater than 0 wt %, and is not particularly limited. Usually, by setting the usage amount of the multifunctional monomer to more than about 0.001 wt % of the monomer component (e.g., more than about 0.01 wt %), the use effect of the multifunctional monomer can be appropriately exerted.

[0129] The method for obtaining the acrylic polymer is not particularly limited, and various polymerization methods known as the synthesis methods of acrylic polymers, such as solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, and photopolymerization, can be appropriately adopted. For example, solution polymerization can be preferably adopted. As a monomer supply method when performing solution polymerization, a one-time feeding method of supplying all monomer raw materials at one time, a continuous supply (drip) method, a batch supply (drip) method, etc. can be appropriately adopted. The polymerization temperature can be appropriately selected according to the types of monomers and solvents used, the type of polymerization initiator, etc., and can be set to about 20°C to 170°C (typically about 40°C to 140°C).

[0130] The solvent (polymerization solvent) used in solution polymerization can be appropriately selected from conventionally known organic solvents. For example, any solvent selected from aromatic compounds such as toluene (typically aromatic hydrocarbons); acetates such as ethyl acetate; aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane; halogenated alkanes such as 1,2-dichloroethane; lower alcohols such as isopropanol (for example, monohydric alcohols having 1 to 4 carbon atoms); ethers such as tert-butyl methyl ether; ketones such as methyl ethyl ketone; etc., or a mixed solvent of two or more can be used.

[0131] The initiator used in the polymerization can be appropriately selected from conventionally known polymerization initiators according to the type of polymerization method. For example, without particular limitation, azo polymerization initiators, peroxide polymerization initiators, redox polymerization initiators based on a combination of peroxide and a reducing agent, substituted ethane polymerization initiators, etc. can be used. As the polymerization initiator, for example, one or more of the substances exemplified as thermal polymerization initiators that can be added to the adhesive described later can be selected and used.

[0132] The amount of the polymerization initiator used can be set to a normal amount corresponding to the polymerization method, polymerization mode, etc., and is not particularly limited. For example, about 0.001 to 5 parts by weight (typically about 0.01 to 2 parts by weight, for example, about 0.01 to 1 part by weight) of the polymerization initiator can be used relative to 100 parts by weight of all monomer components of the polymerization object.

[0133] The molecular weight of the polymer (for example, an acrylic polymer) is not particularly limited and can be set within an appropriate range depending on the required performance, etc. The weight average molecular weight (Mw) of the above polymer is about 1×10 4 The above is suitable, for example, it can be about 10×10 4 By using a polymer having an Mw of a predetermined value or more, cohesive force and adhesive force can be achieved in a well-balanced manner. In some embodiments, the Mw may be 20×10 4 Above, it can be 30×10 4 Above, it can be about 40×10 4 Above, it can be about 50×10 4 For example, it can be about 55×10 4 The upper limit of the Mw of the above polymer is not particularly limited, and can be, for example, about 1000×10 4 Below, it can also be about 100×10 4Here, Mw refers to a value obtained by gel permeation chromatography (GPC) in terms of standard polystyrene. As a GPC apparatus, for example, a model "HLC-8320GPC" (chromatographic column: TSKgelGMH-H(S), manufactured by Tosoh Corporation) can be used.

[0134] (Polymer having ethylenically unsaturated groups)

[0135] In some embodiments, as a polymer, a polymer having an ethylenically unsaturated group such as an acryloyl group, a methacryloyl group, a vinyl group, an allyl group, etc. can be used. According to the adhesive containing the polymer having an ethylenically unsaturated group, by causing the ethylenically unsaturated group possessed by the polymer to react when heated, the adhesive is thermally cured, and easy peelability by heating can be obtained. As a polymer having an ethylenically unsaturated group, for example, a polymer having an ethylenically unsaturated group in a side chain can be used. As a monomer component of the polymer having an ethylenically unsaturated group, one or more of the monomer components exemplified as the above-mentioned polymer can be used within the above-mentioned content range.

[0136] The amount of the ethylenically unsaturated group in the polymer with ethylenically unsaturated groups is not particularly limited. From the viewpoints of thermosetting properties, it is appropriate to set it to 0.01mmol (hereinafter, also referred to as mmol / g) or more relative to each 1g of polymer, and it can be more than 0.1mmol / g, or more than 0.5mmol / g. In addition, it is appropriate to set the amount of the ethylenically unsaturated group in the above-mentioned polymer to less than 10.0mmol / g, and it can be less than 5.0mmol / g, and it can be less than 3.0mmol / g, and it can be less than 2.5mmol / g, and it can be less than 2.0mmol / g.

[0137] The amount of the ethylenically unsaturated group in the polymer is measured by the following method, for example, when the ethylenically unsaturated group is a (meth)acryloyl group.

[0138] First, 0.25 mg of the polymer to be measured is dissolved in 50 mL of THF (tetrahydrofuran), and 15 mL of methanol is further added to obtain a solution. Then, 10 mL of 4N sodium hydroxide aqueous solution is added to the above solution to obtain a mixed solution. Then, the above mixed solution is stirred at a liquid temperature of 40°C for 2 hours. Furthermore, 10.2 mL of 4N methanesulfonic acid solution is added to the above mixed solution and stirred. 5 mL of desalted water is added thereto, followed by 2 mL of methanol to prepare a measurement solution.

[0139] The (meth)acrylic acid content in the measurement solution was measured by HPLC (High Performance Liquid Chromatography) method (absolute standard curve method), and the ethylenically unsaturated group content was calculated.

[0140] (HPLC measurement conditions)

[0141] Chromatographic column: Synergi 4μPolar-RP 80A (4.6 mm × 250 mm) manufactured by Phenomenex

[0142] Column temperature: 40°C

[0143] Flow rate: 1.0mL / min

[0144] Detector wavelength: 210nm

[0145] Eluent: THF (for HPLC) 55 / buffer (containing 0.2% phosphoric acid, 0.2% triethylamine) 45

[0146] Aqueous solution injection volume: 5μL

[0147] As a method for measuring the content of other ethylenically unsaturated groups other than (meth)acryloyl groups, there can be mentioned a method for measuring the bromine value in accordance with JIS K2605: 1996. In this measurement method, the content of other ethylenically unsaturated groups other than (meth)acryloyl groups can be determined by converting the number of grams of bromine (Br2) added to 100 g of the polymer to be measured into the number of moles of bromine (Br2) added to 1 g of the polymer.

[0148] The method of introducing ethylenically unsaturated groups into polymers is not particularly limited. For example, it is possible to preferably adopt a method in which a compound having a functional group (functional group B) and an ethylenically unsaturated group that can react with a functional group (functional group A) introduced into an acrylic polymer by copolymerization and reacts in a manner that the ethylenically unsaturated group does not disappear (typically a condensation reaction or an addition reaction). Examples of combinations of functional group A and functional group B include a combination of a carboxyl group and an epoxy group, a combination of a carboxyl group and an aziridine group, a combination of a hydroxyl group and an isocyanate group, and the like. Among them, from the viewpoint of reaction tracking, a combination of a hydroxyl group and an isocyanate group is preferred. From the viewpoints of polymer design, it is particularly preferred that the acrylic polymer has a hydroxyl group and the above-mentioned compound has an isocyanate group.

[0149] The compound having an ethylenically unsaturated group may have a functional group B that can react with the functional group A as described above. As a suitable example of such a compound, for example, a monomer containing an isocyanate group (a compound containing an isocyanate group) exemplified as other monomers that can be used for the polymerization of an acrylic polymer can be cited. Among them, 2-(meth)acryloyloxyethyl isocyanate is more preferred. The acrylic polymer having an ethylenically unsaturated group can be obtained by reacting the isocyanate group of the compound containing an isocyanate group having an ethylenically unsaturated group with the hydroxyl group of the acrylic polymer to form a bond (specifically, a carbamate bond).

[0150] The amount of the compound having an ethylenically unsaturated group (e.g., a monomer containing an isocyanate group) added is not particularly limited, and can be 1:1 molar amount (M) of the functional group A in the polymer. A ) and the molar ratio (M B ) molar ratio (M A / M B ) is set so as to be in the range of about 0.5 to 2 (for example, 1 to 1.5).

[0151] In the method of using a polymer having an ethylenically unsaturated group as a polymer, the content of the polymer having an ethylenically unsaturated group in the adhesive composition is not particularly limited. In some methods, the amount of the polymer having an ethylenically unsaturated group in the non-volatile component (solid component) of the adhesive composition can be about 50% by weight or less (e.g., less than 50% by weight), less than 30% by weight, less than 10% by weight, or less than 1% by weight. The technology disclosed herein can preferably be implemented using an adhesive that does not substantially contain a polymer having an ethylenically unsaturated group.

[0152] In some embodiments, as the polymer, a polymer substantially free of ethylenically unsaturated groups such as acryloyl, methacryloyl, vinyl, and allyl groups (the amount of ethylenically unsaturated groups is less than 0.01 mmol / g) may be used.

[0153] (Multifunctional monomer)

[0154] In some ways, in addition to the above-mentioned polymer, it is preferred that the adhesive also contains a multifunctional monomer. By making the multifunctional monomer be included in the adhesive in a state before reaction (unreacted), the multifunctional monomer reacts when heated at high temperature, so that the adhesive force is reduced or the rise of the peeling force is suppressed, and easy peeling by heating can be achieved. More specifically, usually, when heated at high temperature in a state of being attached to an adherend, the adhesive will be adsorbed on the surface of the adherend. Therefore, the adhesive force of the adhesive to the adherend is enhanced, and heavy peeling will occur. In some ways, by making the adhesive contain a multifunctional monomer, the reaction of the multifunctional monomer is carried out rapidly when heated, and the adhesive curing can be carried out before the adsorption of the adhesive to the adherend. Thus, the adhesive force to the adherend can be reduced. Further, even if the heating continues afterwards, the adhesive force of the adhesive to the adherend will not rise, but is maintained within a specified range, so the adhesive will play an excellent easy peeling by heating. It should be noted that the technology disclosed herein is not limited to the above explanation. The multifunctional monomer can be used alone or in combination of two or more.

[0155] It should be noted that in this specification, the so-called multifunctional monomer refers to a polymerizable compound having more than two ethylenically unsaturated groups in one molecule, and also includes substances called oligomers. The above-mentioned ethylenically unsaturated groups function as polymerizable functional groups (typically free radical polymerizable functional groups). Examples of ethylenically unsaturated groups possessed by multifunctional monomers include acryloyl, methacryloyl, vinyl and allyl groups, but are not limited to these. Suitable examples of ethylenically unsaturated groups include acryloyl and methacryloyl. Among them, acryloyl is preferred. Hereinafter, compounds having more than two acryloyl and / or methacryloyl groups are sometimes referred to as multifunctional acrylic monomers. In addition, compounds having more than two vinyl groups are sometimes referred to as multifunctional vinyl monomers.

[0156] The number of ethylenically unsaturated groups contained in a molecule of a multifunctional monomer is preferably 3 or more, more preferably 4 or more, further preferably 5 or more, and may be 6 or more. The more ethylenically unsaturated groups there are in a multifunctional monomer, the better the curability during heating, and the easier it is to obtain a tendency to be easily peelable by heating. In addition, by using a multifunctional monomer with more ethylenically unsaturated groups (functional groups), it is possible to obtain easy peelability by heating with a relatively small amount of use. This reduces the amount of released gas from the multifunctional monomer, which is advantageous. The upper limit of the number of ethylenically unsaturated groups in a molecule of a multifunctional monomer is not limited to a specific range, for example, it may be less than 50, less than 40, less than 30, less than 20, or less than 15. In some ways, the number of ethylenically unsaturated groups in a molecule of a multifunctional monomer may be, for example, less than 10, less than 8, or less than 6. By having a multifunctional monomer with the above-mentioned number of ethylenically unsaturated groups, it is easy to achieve good adhesion and easy peelability by heating, and the storage stability is also excellent.

[0157] As the multifunctional monomer, various multifunctional acrylate monomers and multifunctional vinyl monomers having 2 or more ethylenically unsaturated groups can be used. Among them, multifunctional acrylate monomers can be preferably used. Although not particularly limited, multifunctional acrylate monomers tend to exhibit desired properties with good compatibility when used in combination with acrylic polymers. Multifunctional acrylate monomers and multifunctional vinyl monomers can be used alone or in combination of two or more.

[0158] Examples of the polyfunctional monomer include 1,6-hexanediol di(meth)acrylate, 1,12-dodecanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, allyl (meth)acrylate, alkylene oxide-modified bisphenol A di(meth)acrylate, alkylene oxide-modified neopentyl glycol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, dimethylol dicyclopentane di(meth)acrylate, vinyl (meth)acrylate, diethylene glycol di(meth)acrylate, Bifunctional monomers such as alkenylbenzene; trifunctional monomers such as trimethylolpropane tri(meth)acrylate, trimethylolpropane ethoxy tri(meth)acrylate, glycerol propoxy triacrylate, tetramethylolmethane tri(meth)acrylate, and pentaerythritol tri(meth)acrylate; quadrifunctional monomers such as pentaerythritol alkoxy tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, and pentaerythritol tetra(meth)acrylate; pentafunctional monomers such as sorbitol penta(meth)acrylate and dipentaerythritol penta(meth)acrylate; hexafunctional monomers such as dipentaerythritol hexa(meth)acrylate, sorbitol hexa(meth)acrylate, alkylene oxide-modified hexa(meth)acrylate, and caprolactone-modified dipentaerythritol hexa(meth)acrylate; and epoxy acrylates, polyester acrylates, and urethane acrylates having two or more functionalities. Among them, preferred examples include 1,6-hexanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and dipentaerythritol hexa(meth)acrylate. Among them, dipentaerythritol hexa(meth)acrylate is particularly preferred.

[0159] Although not particularly limited, it is appropriate to use a multifunctional monomer with a molecular weight of 100 or more as a multifunctional monomer. In some preferred embodiments, the molecular weight of the multifunctional monomer can be, for example, 150 or more, 250 or more, 300 or more, 350 or more, 400 or more, 450 or more, or 500 or more. In addition, the molecular weight of the multifunctional monomer is generally about 100,000 or less, for example, about 10,000 or less (for example, less than 10,000) is appropriate, preferably 5,000 or less (for example, less than 5,000), 1,500 or less, 1,000 or less (for example, less than 1,000), 800 or less, or 600 or less. The use of a multifunctional monomer with a molecular weight in the above range is advantageous, for example, in terms of the preparation and coating properties of the adhesive composition. It should be noted that the above molecular weight is a molecular weight calculated based on the manufacturer's nominal value or molecular structure. For a polyfunctional monomer having a molecular weight greater than or equal to a predetermined value, a value of a weight average molecular weight (Mw) in terms of standard polystyrene obtained by GPC may be employed.

[0160] In some preferred embodiments, as a multifunctional monomer, a multifunctional monomer having a weight loss rate of 1% or less (specifically, 1.0% or less) when reaching 180°C in TGA under a heating condition of 10°C / min is used. By using a heat-resistant multifunctional monomer having the above-mentioned 180°C heating weight loss rate of 1% or less (hereinafter, also referred to as a "heat-resistant multifunctional monomer"), the adhesive has heat-resistant peelability based on the use of the multifunctional monomer, and the generation of released gas during heating is suppressed. By using the above-mentioned heat-resistant multifunctional monomer, it is possible to achieve both heat-resistant peelability and reduced released gas. From the viewpoint of reduced released gas, in some preferred embodiments, the 180°C heating weight loss rate of the heat-resistant multifunctional monomer is 0.9% or less, more preferably 0.8% or less, further preferably 0.7% or less, particularly preferably 0.6% or less, and may also be 0.5% or less. The lower limit of the 180°C heating weight loss rate of the heat-resistant multifunctional monomer is theoretically 0%, but can be 0.1% or more, 0.2% or more, or 0.3% or more in practice. The heat-resistant multifunctional monomer can be used alone or in combination of two or more.

[0161] The 180° C. heating weight loss rate of the polyfunctional monomer can be specifically measured using a differential thermal analyzer (manufactured by TA Instruments, trade name “Discovery TGA”) under measurement conditions of a temperature increase of 10° C. / min, an air atmosphere, and a flow rate of 25 mL / min.

[0162] The content of the heat-resistant multifunctional monomer in the adhesive is not particularly limited. In some embodiments, it is appropriate to be 20 parts by weight or more relative to 100 parts by weight of the polymer (specifically, the base polymer. Suitable acrylic polymer) contained in the adhesive, and it is preferred to be 30 parts by weight or more. By making the adhesive contain a sufficient amount of heat-resistant multifunctional monomers, when heated, the multifunctional monomers will react rapidly, and the adhesive is thermally cured, thereby achieving easy peeling by heating. The appropriate amount of the heat-resistant multifunctional monomer can be different according to its molecular weight, the number of functional groups, etc. In some preferred embodiments, from the viewpoint of easy peeling by heating, it is appropriate to set the amount of the heat-resistant multifunctional monomer relative to 100 parts by weight of the above-mentioned polymer to be 50 parts by weight or more, preferably 60 parts by weight or more, more preferably 70 parts by weight or more, further preferably 80 parts by weight or more, particularly preferably 90 parts by weight or more, and can also be 100 parts by weight or more. The upper limit of the content of the heat-resistant multifunctional monomer in the adhesive is not particularly limited, and can be set in a manner to achieve the desired adhesive properties. In some embodiments, from the perspective of compatibility with a polymer (specifically, a base polymer, such as an acrylic polymer), the amount of the heat-resistant multifunctional monomer relative to 100 parts by weight of the above-mentioned polymer is appropriately set to about 200 parts by weight or less, preferably 160 parts by weight or less, more preferably 150 parts by weight or less, further preferably 140 parts by weight or less, and can be 120 parts by weight or less, or can be 90 parts by weight or less.

[0163] The content of the multifunctional monomer in the adhesive is not particularly limited. In some embodiments, the amount of the multifunctional monomer relative to 100 parts by weight of the polymer (specifically, the base polymer. Suitable acrylic polymer) contained in the adhesive can be 20 parts by weight or more, 30 parts by weight or more is appropriate, and 50 parts by weight or more is preferred. By including a sufficient amount of multifunctional monomers in the adhesive, the multifunctional monomers react rapidly when heated, and the adhesive is thermally cured, thereby achieving easy peeling by heating. The appropriate amount of the multifunctional monomer can be different according to its molecular weight, the number of functional groups, etc., and generally, from the viewpoint of easy peeling by heating, the amount of the multifunctional monomer relative to 100 parts by weight of the above-mentioned polymer is preferably 60 parts by weight or more, more preferably 70 parts by weight or more, further preferably 80 parts by weight or more, particularly preferably 90 parts by weight or more, and can also be 100 parts by weight or more. The upper limit of the content of the multifunctional monomer in the adhesive is not particularly limited, and can be set in a manner to achieve the desired adhesive properties. In some embodiments, from the perspective of compatibility with a polymer (specifically, a base polymer, such as an acrylic polymer), the amount of the multifunctional monomer relative to 100 parts by weight of the above-mentioned polymer is appropriately set to about 200 parts by weight or less, preferably 160 parts by weight or less, more preferably 150 parts by weight or less, further preferably 140 parts by weight or less, and can be 120 parts by weight or less, or can also be 90 parts by weight or less.

[0164] In some other embodiments, the adhesive may be substantially free of multifunctional monomers, or the amount of multifunctional monomers used may be limited. For example, as a polymer, in the method of using a polymer having the above-mentioned ethylenically unsaturated groups, the multifunctional monomer may be composed of a specified amount or less. In the above-mentioned method, the amount of the multifunctional monomer relative to 100 parts by weight of the polymer (specifically, the base polymer. For example, an acrylic polymer) may be less than 50 parts by weight, less than 30 parts by weight, less than 10 parts by weight, less than 3 parts by weight, or less than 1 part by weight.

[0165] In some embodiments, the adhesive contains the above-mentioned polymer (specifically, a base polymer, such as an acrylic polymer) and a multifunctional monomer (such as a multifunctional acrylic monomer). In some preferred embodiments, from the viewpoint of effectively exerting the reduction in peeling force caused by heating, it is appropriate that the total proportion of the above-mentioned polymer and the multifunctional monomer to the whole adhesive is 50% by weight or more (for example, more than 50% by weight and less than 100% by weight), preferably 70% by weight or more, more preferably 80% by weight or more, further preferably 90% by weight or more, and may also be 95% by weight or more.

[0166] (Monofunctional monomer)

[0167] In addition, in the adhesive, according to the expectation, one or more monofunctional monomers containing one ethylenically unsaturated group in one molecule may also be included. The monofunctional monomer can be used within the scope of not damaging the effect brought by the technology disclosed herein. As the monofunctional monomer, known monofunctional acrylate monomers and vinyl monomers can be used. Although not particularly limited, it is appropriate to set the content of the monofunctional monomer in the adhesive to about 100 parts by weight or less (0 parts by weight or more and 100 parts by weight or less, for example, less than 100 parts by weight) relative to 100 parts by weight of the multifunctional monomer, and it may be less than 50 parts by weight, less than 30 parts by weight, less than 10 parts by weight, or less than 1 part by weight. The technology disclosed herein can be implemented in a manner that the adhesive does not substantially contain monofunctional monomers.

[0168] (Thermal polymerization initiator)

[0169] In some embodiments, the adhesive preferably contains a thermal polymerization initiator. Here, the so-called thermal polymerization initiator refers to a polymerization initiator that generates free radicals by heating. By including the thermal polymerization initiator in the adhesive in a pre-reaction (unreacted) state, the thermal polymerization initiator reacts when heated at a high temperature, thereby reducing the adhesive force or suppressing the increase in the adhesive force, and it is possible to achieve ideal heat-easy peelability.

[0170] The thermal polymerization initiator is not particularly limited, and for example, a peroxide polymerization initiator, an azo polymerization initiator, a redox polymerization initiator based on a combination of a peroxide and a reducing agent, a substituted ethane polymerization initiator, and the like can be used. Specifically, examples include: persulfates such as potassium persulfate and ammonium persulfate; peroxide compounds such as benzoyl peroxide (BPO), tert-butyl hydroperoxide, and hydrogen peroxide; azo compounds such as 2,2'-azobisisobutyronitrile (AIBN) and 2,2'-azobis(N-butyl-2-methylpropionamide); substituted ethane initiators such as phenyl-substituted ethane; redox initiators based on a combination of peroxides and reducing agents such as a combination of persulfate and sodium bisulfite, a combination of peroxide and sodium ascorbate, and the like. These thermal polymerization initiators can be used alone or in combination of two or more. Although not particularly limited, in the technology disclosed herein, as the thermal polymerization initiator contained in the adhesive, it can be preferably implemented in the form of a peroxide polymerization initiator, an azo polymerization initiator, or a combination of both.

[0171] In some embodiments, as a thermal polymerization initiator, a thermal polymerization initiator with a 10-hour half-life temperature of, for example, 50°C or more can be preferably used. Here, the so-called 10-hour half-life temperature of the polymerization initiator refers to the temperature at which the concentration of the initiator becomes half after 10 hours, and is used as an index to indicate the decomposition rate of the polymerization initiator and the thermal decomposition property (free radical generation property) at a specified temperature. In this specification, as the 10-hour half-life temperature of the thermal polymerization initiator, the nominal value recorded in the manufacturer's catalog, etc. is adopted. For the case where there is no manufacturer's nominal value, the value measured using an appropriate solvent (such as toluene) can be adopted. Although it is believed that the thermal decomposition property of the thermal polymerization initiator in the adhesive is different from the thermal decomposition property in the solvent, the thermal polymerization initiator with a high 10-hour half-life temperature has a tendency to have excellent heat resistance and excellent storage stability. From such a point of view, the 10-hour half-life temperature of the thermal polymerization initiator can be above 55°C, above 60°C, above 65°C, or above 70°C. In some other embodiments, the 10-hour half-life temperature of the thermal polymerization initiator may be above 80°C, above 90°C, or above 100°C (e.g., above 100°C). In addition, the upper limit of the 10-hour half-life temperature of the thermal polymerization initiator is, for example, below 150°C, and it is appropriate to be below 120°C. In some embodiments, the 10-hour half-life temperature of the thermal polymerization initiator is appropriately about 100°C or below (e.g., below 100°C), and may be below 95°C, below 90°C, below 85°C, or below 80°C.

[0172] In some embodiments, as a thermal polymerization initiator, it is preferred to use at least an azo polymerization initiator. When an azo polymerization initiator is used as a thermal polymerization initiator, there is a tendency for the amount of released gas from the adhesive to decrease. In addition, according to the adhesive containing an azo polymerization initiator as a thermal polymerization initiator, even in the case of long-term storage, when there is a temperature change during storage, etc., after storage, the desired heat resistance and easy peelability can be maintained. By using an azo polymerization initiator as a thermal polymerization initiator, an adhesive with good storage stability can be formed. As a reason for this, it is believed that compared with other types of polymerization initiators, the azo polymerization initiator has good thermal stability in the adhesive, but the technology disclosed herein is not limited to the above-mentioned investigation. Azo polymerization initiators can be used alone or in combination of two or more.

[0173] The azo polymerization initiator used in the art disclosed herein is not particularly limited, and any of azonitrile compounds, azoamide compounds, azoester compounds, alkylazo compounds, azoamidine compounds, azoimidazoline compounds, and polymeric azo compounds can be used. Specific examples of the azo polymerization initiator include AIBN, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 4,4-azobis(4-cyanovaleric acid), 2,2'-azobis(N-butyl-2-methylpropionamide), dimethyl 2,2'-azobis(2-methylpropionate), 1,1'-azobis(1-cyclohexanecarboxylic acid) dimethyl ester, 2,2'-azobis(2-methylpropane), 2,2'-azobis(2 ,4,4-trimethylpentane), 2-tert-butylazo-2-cyanopropane, 4,4'-azobis(3,3,4,4,5,5,6,6,7,7,8,8,8-tri-N,N'-dimethyleneisobutylamidine), 2,2'-azobis(2-methylpropionamidine) disulfate, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] hydrate, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane] dihydrochloride, azocumene, etc.

[0174] Although not particularly limited, as the above-mentioned azo polymerization initiator, an azo polymerization initiator having a 10-hour half-life temperature of, for example, 50°C or more can be preferably used. The above-mentioned thermal polymerization initiator with a high 10-hour half-life temperature tends to have excellent heat resistance and excellent storage stability. From the above viewpoint, the 10-hour half-life temperature of the above-mentioned azo polymerization initiator is preferably 55°C or more, more preferably 60°C or more, further preferably 65°C or more, particularly preferably 70°C or more, can be 80°C or more, can be 90°C or more, and can also be 100°C or more (for example, more than 100°C). The upper limit of the 10-hour half-life temperature of the azo polymerization initiator is, for example, 150°C or less, and 120°C or less is appropriate. In some preferred embodiments, an azo polymerization initiator having a 10-hour half-life temperature of, for example, 100°C or less (for example, less than 100°C, 95°C or less, or 90°C or less) can be used.

[0175] The content of the azo polymerization initiator in the adhesive is not particularly limited, and can be set to, for example, 0.1 weight part or more (0.10 weight part or more) relative to 100 weight parts of the polymer (specifically, the base polymer. For example, an acrylic polymer) contained in the adhesive. For example, by including a prescribed amount or more of an azo polymerization initiator in the adhesive, a sufficient amount of the azo polymerization initiator can react rapidly. Thus, it is possible to achieve easy peeling by heating ideally. In addition, the adhesive can have good storage stability by including an azo polymerization initiator. From the above viewpoint, the amount of the azo polymerization initiator relative to 100 weight parts of the above-mentioned polymer is preferably 0.15 weight part or more, more preferably 0.20 weight part or more, further preferably 0.25 weight part or more, can be 0.30 weight part or more, can be 0.35 weight part or more, can be 0.40 weight part or more, can be 0.45 weight part or more, and can also be 0.50 weight part or more. The upper limit of the content of the azo polymerization initiator in the adhesive is not particularly limited, and can be appropriately set in a manner that does not damage the adhesive properties such as bonding strength and storage stability. In some embodiments, the amount of the azo polymerization initiator relative to 100 parts by weight of the polymer (specifically, the base polymer. For example, an acrylic polymer) is, for example, less than 3 parts by weight, which is appropriate, preferably less than 2.5 parts by weight, more preferably less than 2.0 parts by weight, further preferably less than 1.5 parts by weight, particularly preferably less than 1.2 parts by weight (for example, less than 1.1 parts by weight), can be less than 1.0 parts by weight (for example, less than 1.0 parts by weight), can be less than 0.8 parts by weight, and can also be less than 0.6 parts by weight (for example, less than 0.4 parts by weight). In addition, by limiting the amount of the azo polymerization initiator used, the generation of released gas from the azo polymerization initiator can be suppressed.

[0176] In the mode where the adhesive includes a multifunctional monomer, the content of the azo polymerization initiator in the adhesive can also be determined by the relative relationship with the multifunctional monomer. In some modes, from the viewpoint of the probability of contact with the multifunctional monomer, it is appropriate to set the amount of the azo polymerization initiator relative to 100 parts by weight of the multifunctional monomer to be 0.1 parts by weight or more (0.10 parts by weight or more), preferably 0.15 parts by weight or more, more preferably 0.20 parts by weight or more, further preferably 0.25 parts by weight or more, can be 0.30 parts by weight or more, can be 0.35 parts by weight or more, can be 0.40 parts by weight or more, can be 0.45 parts by weight or more, and can also be 0.50 parts by weight or more. In some embodiments, the amount of the azo polymerization initiator relative to 100 parts by weight of the multifunctional monomer is, for example, appropriately about 10 parts by weight or less, preferably 5 parts by weight or less, more preferably 3 parts by weight or less, further preferably 1.5 parts by weight or less, particularly preferably less than 1.2 parts by weight (for example, less than 1.1 parts by weight), may be less than 1.0 parts by weight (for example, less than 1.0 parts by weight), may be less than 0.8 parts by weight, or may be less than 0.6 parts by weight (for example, less than 0.4 parts by weight).

[0177] In some embodiments, the adhesive contains only an azo polymerization initiator as a thermal polymerization initiator, or may contain an azo polymerization initiator and a thermal polymerization initiator different from the azo polymerization initiator (non-azo polymerization initiator). In the embodiment using only an azo polymerization initiator, the effect of using the azo polymerization initiator can be maximized, and in the embodiment using an azo polymerization initiator and a non-azo polymerization initiator together, the effects and characteristics based on the azo polymerization initiator and the non-azo polymerization initiator can be utilized. In some embodiments, it is appropriate to set the proportion of the azo polymerization initiator to the total thermal polymerization initiator contained in the adhesive to about 10% by weight or more. From the perspective of effectively exerting the effect of the azo polymerization initiator, it is preferably 30% by weight or more, more preferably 40% by weight or more, and further preferably 50% by weight or more (for example, more than 50% by weight), and can be 55% by weight or more, or 60% by weight or more. In some other embodiments, the proportion of the azo polymerization initiator to the total thermal polymerization initiator is, for example, about 65% by weight or more, 75% by weight or more, 85% by weight or more, 95% by weight or more, or 99% by weight or more. In addition, the upper limit of the proportion of the azo polymerization initiator to the total thermal polymerization initiator is 100% by weight, for example, 90% by weight or less, 80% by weight or less, 70% by weight or less, or 60% by weight or less.

[0178] In addition, in some preferred embodiments, the adhesive includes a peroxide-based polymerization initiator as a thermal polymerization initiator. Thus, by utilizing the high initiation efficiency of the peroxide-based polymerization initiator (specifically, an organic peroxide-based polymerization initiator), even when the amount of the multifunctional monomer used is relatively small, there is also a tendency to fully thermally cure and easily achieve easy heating and peeling properties. In some embodiments, it is appropriate that the ratio of the thermal polymerization initiator contained in the adhesive as a whole is set to about 10% by weight or more. From the perspective of effectively exerting the effect of the peroxide-based polymerization initiator, it is preferably more than 30% by weight, more preferably more than 40% by weight, and further preferably more than 50% by weight (for example, more than 50% by weight), can be more than 55% by weight, or can be more than 60% by weight. In some other embodiments, the ratio of the peroxide-based polymerization initiator to the above-mentioned thermal polymerization initiator as a whole is, for example, about 65% by weight or more, can be more than 75% by weight, can be more than 85% by weight, can be more than 95% by weight, or can be more than 99% by weight. The upper limit of the ratio of the peroxide-based polymerization initiator to the total thermal polymerization initiator is 100 wt %, and may be, for example, 90 wt % or less, 80 wt % or less, 70 wt % or less, or 60 wt % or less.

[0179] The total amount of thermal polymerization initiators contained in the adhesive (when containing more than two kinds, the total content of more than two kinds) is not particularly limited and can be set in a manner to achieve easy peeling by heating. In some embodiments, the total amount of the above-mentioned thermal polymerization initiators is, for example, 0.1 parts by weight or more relative to 100 parts by weight of the polymer (specifically, the base polymer. For example, an acrylic polymer) contained in the adhesive. By including the above-mentioned amount of thermal polymerization initiators in the adhesive, a sufficient amount of thermal polymerization initiators will react rapidly and can have easy peeling by heating. From the viewpoint of easy peeling by heating, the total amount of thermal polymerization initiators relative to 100 parts by weight of the above-mentioned polymer is preferably 0.2 parts by weight or more, more preferably 0.3 parts by weight or more, further preferably 0.4 parts by weight or more, and can also be 0.5 parts by weight or more. The upper limit of the total amount of thermal polymerization initiators in the adhesive is not particularly limited. In some embodiments, the total amount of thermal polymerization initiators relative to 100 parts by weight of the polymer (specifically, the base polymer. For example, an acrylic polymer) is, for example, about 10 parts by weight or less, can be 5 parts by weight or less, and can also be 3 parts by weight or less. In some preferred embodiments, the total amount of the above-mentioned thermal polymerization initiator is, for example, less than 3 parts by weight, which is appropriate, preferably less than 2.5 parts by weight, more preferably less than 2.0 parts by weight, further preferably less than 1.5 parts by weight, particularly preferably less than 1.2 parts by weight (for example, less than 1.1 parts by weight), less than 1.0 parts by weight (for example, less than 1.0 parts by weight), less than 0.9 parts by weight, less than 0.8 parts by weight, less than 0.7 parts by weight, or less than 0.6 parts by weight. By setting the total amount of the thermal polymerization initiator within a specified range, it is possible to obtain adhesive properties such as adhesion, storage stability, and ideally achieve efficient thermosetting properties and easy peeling by heating. In addition, by limiting the amount of the thermal polymerization initiator used, it is possible to suppress the generation of released gas from the thermal polymerization initiator.

[0180] In some other embodiments, the total amount of the thermal polymerization initiator contained in the adhesive is, for example, 1.0 part by weight or more, 1.2 parts by weight or more, 1.5 parts by weight or more, 2.0 parts by weight or more, 2.5 parts by weight or more, 3.0 parts by weight or more, or 3.5 parts by weight or more relative to 100 parts by weight of the polymer (specifically, the base polymer, such as an acrylic polymer) contained in the adhesive. For example, in the embodiment of using a polymer having the above-mentioned ethylenically unsaturated group as the polymer, by increasing the amount of the above-mentioned thermal polymerization initiator, it is easy to obtain heat-peelable properties.

[0181] In the mode that the adhesive includes a multifunctional monomer, the content of the thermal polymerization initiator in the adhesive can also be determined by the relative relationship with the multifunctional monomer. In some ways, from the viewpoint of the probability of contact with the multifunctional monomer, it is appropriate to set the amount of the thermal polymerization initiator relative to 100 parts by weight of the multifunctional monomer to be 0.1 parts by weight or more, preferably 0.2 parts by weight or more, more preferably 0.3 parts by weight or more, further preferably 0.4 parts by weight or more, and also 0.5 parts by weight or more. In some ways, the amount of the thermal polymerization initiator relative to 100 parts by weight of the multifunctional monomer is, for example, about 10 parts by weight or less, preferably 5 parts by weight or less, more preferably 3 parts by weight or less, further preferably 1.5 parts by weight or less, particularly preferably less than 1.2 parts by weight (for example, less than 1.1 parts by weight), can be less than 1.0 parts by weight (for example, less than 1.0 parts by weight), can be less than 0.9 parts by weight, can be less than 0.8 parts by weight, can be less than 0.7 parts by weight, and can also be less than 0.6 parts by weight.

[0182] (Crosslinking agent)

[0183] In the adhesive composition that can be used for the formation of adhesive, mainly for the purpose of crosslinking in the adhesive or crosslinking of the adhesive with its adjacent surface, a crosslinking agent can be contained as needed. The crosslinking agent is typically contained in the adhesive in the form after the crosslinking reaction. Through the use of the crosslinking agent, the cohesive force of the adhesive can be appropriately adjusted.

[0184] The kind of cross-linking agent is not particularly limited, and can be selected from among the cross-linking agents known in the past, for example, according to the composition of adhesive, in the mode that the cross-linking agent plays appropriate cross-linking function in adhesive. As usable cross-linking agent, isocyanate cross-linking agent, epoxy cross-linking agent, oxazoline cross-linking agent, aziridine cross-linking agent, carbodiimide cross-linking agent, melamine cross-linking agent, urea cross-linking agent, metal alkoxide cross-linking agent, metal chelate cross-linking agent, metal salt cross-linking agent, hydrazine cross-linking agent, amine cross-linking agent etc. can be exemplified. They can be used alone or in combination of two or more. From the viewpoint of realizing adhesion and cohesion well at the same time in balanced, preferably isocyanate cross-linking agent, epoxy cross-linking agent, oxazoline cross-linking agent, aziridine cross-linking agent, carbodiimide cross-linking agent, particularly preferably isocyanate cross-linking agent.

[0185] As the isocyanate crosslinking agent, a polyfunctional isocyanate compound having two or more functions can be used. For example, aromatic isocyanates such as toluene diisocyanate, xylene diisocyanate, polymethylene polyphenyl diisocyanate, tris(p-isocyanatephenyl)thiophosphate, and diphenylmethane diisocyanate; alicyclic isocyanates such as isophorone diisocyanate; aliphatic isocyanates such as hexamethylene diisocyanate; and the like can be cited. Examples of commercially available products include isocyanate adducts such as trimethylolpropane / toluene diisocyanate trimer adduct (manufactured by Tosoh Corporation, trade name “Coronate L”), trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Tosoh Corporation, trade name “Coronate HL”), isocyanurate of hexamethylene diisocyanate (manufactured by Tosoh Corporation, trade name “Coronate HX”), and trimethylolpropane / xylene diisocyanate adduct (manufactured by Mitsui Chemicals, Inc., trade name “Takenate D-110N”).

[0186] As the epoxy crosslinking agent, a substance having two or more epoxy groups in one molecule can be used without particular limitation. An epoxy crosslinking agent having 3 to 5 epoxy groups in one molecule is preferred. Specific examples of epoxy crosslinking agents include N,N,N',N'-tetraglycidyl meta-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, polyglycerol polyglycidyl ether, and the like. Commercially available products of epoxy crosslinking agents include trade names "TETRAD-X" and "TETRAD-C" manufactured by Mitsubishi Gas Chemical, trade name "EPICLON CR-5L" manufactured by DIC, trade name "Denacol EX-512" manufactured by Nagase Chemtex, trade name "TEPIC-G" manufactured by Nissan Chemical Industries, Ltd., and the like.

[0187] As the oxazoline crosslinking agent, any oxazoline crosslinking agent having one or more oxazoline groups in one molecule can be used without particular limitation.

[0188] Examples of the aziridine crosslinking agent include trimethylolpropane tris[3-(1-aziridinyl)propionate] and trimethylolpropane tris[3-(1-(2-methyl)aziridinyl propionate)].

[0189] As the carbodiimide-based crosslinking agent, a low molecular weight compound or a high molecular weight compound having two or more carbodiimide groups can be used.

[0190] The amount used when a cross-linking agent is used (the total amount thereof when two or more cross-linking agents are used) is not particularly limited. From the perspective of realizing an adhesive that exhibits adhesive properties such as bonding force and cohesive force in a well-balanced manner, the amount of the cross-linking agent used is an amount greater than 0 parts by weight relative to 100 parts by weight of the polymer (specifically, the base polymer. For example, an acrylic polymer) contained in the adhesive. The amount of the cross-linking agent used can be, for example, 0.001 parts by weight or more, 0.01 parts by weight or more, 0.1 parts by weight or more, or 0.5 parts by weight or more relative to 100 parts by weight of the above-mentioned polymer. In some embodiments, the amount of the cross-linking agent used is, for example, 1 part by weight or more, 1.5 parts by weight or more, 2 parts by weight or more, or 2.5 parts by weight or more relative to 100 parts by weight of the above-mentioned polymer. The upper limit of the amount of cross-linking agent used is not particularly limited. It is appropriate to set it to about 20 parts by weight or less relative to 100 parts by weight of the above-mentioned polymer (specifically, the base polymer, such as an acrylic polymer). In some embodiments, it is preferably 10 parts by weight or less, and can be 7 parts by weight or less, or 5 parts by weight or less.

[0191] In order to more effectively carry out the cross-linking reaction, a cross-linking catalyst can be used. As the cross-linking catalyst, metal cross-linking catalysts such as tetra-n-butyl titanate, tetraisopropyl titanate, triacetylacetonate iron, butyl tin oxide, dioctyltin dilaurate, etc. are exemplified. The amount of the cross-linking catalyst used is not particularly limited. The amount of the cross-linking catalyst used can be set to about 0.0001 parts by weight or more, about 0.001 parts by weight or more, or about 0.005 parts by weight or more relative to 100 parts by weight of the polymer (specifically, the base polymer. For example, an acrylic polymer) contained in the adhesive, for example, 0.0001 parts by weight or more, about 0.001 parts by weight or more, or about 0.005 parts by weight or more, etc., in addition, it can be set to about 1 part by weight or less, about 0.1 parts by weight or less, or about 0.05 parts by weight or less, etc.

[0192] The adhesive composition used for forming the adhesive may contain a compound that produces keto-enol tautomerism as a crosslinking retarder as desired. For example, in an adhesive composition containing an isocyanate crosslinking agent or an adhesive composition that can be used in combination with an isocyanate crosslinking agent, a compound that produces keto-enol tautomerism may be preferably used. Thus, the pot life of the adhesive composition may be extended.

[0193] As compounds that produce keto-enol tautomerism, various β-dicarbonyl compounds can be used. As specific examples, β-diketones such as acetylacetone and 2,4-hexanedione; acetoacetic acid esters such as methyl acetoacetate and ethyl acetoacetate; propionylacetic acid esters such as ethyl propionylacetate; isobutyrylacetic acid esters such as ethyl isobutyrylacetate; malonates such as methyl malonate and ethyl malonate; and the like. Among them, acetylacetone and acetoacetic acid esters can be cited as suitable compounds. The compound that produces keto-enol tautomerism can be used alone or in combination of two or more.

[0194] The amount of the compound that produces keto-enol tautomerism used can be, for example, from 0.1 part by weight to 20 parts by weight relative to 100 parts by weight of the polymer (specifically, the base polymer, for example, an acrylic polymer) contained in the adhesive, and it is appropriate to set it to from 0.5 part by weight to 15 parts by weight. For example, it can be from 1 part by weight to 10 parts by weight, and it can also be from 1 part by weight to 5 parts by weight.

[0195] (Other ingredients)

[0196] The adhesive may contain various additives commonly used in the adhesive composition field such as adhesion imparting agents, silane coupling agents, release force modifiers (surfactants, etc.), viscosity modifiers (such as tackifiers), leveling agents, plasticizers, fillers, colorants such as pigments and dyes, stabilizers, preservatives, and anti-aging agents as needed. For such various additives, conventionally known additives can be used by conventional methods, and since they do not particularly characterize the present invention, detailed descriptions are omitted.

[0197] It should be noted that the technology disclosed herein can achieve desired adhesive properties such as bonding strength without using an adhesion-imparting agent. In some embodiments, the content of the adhesion-imparting agent in the adhesive can be, for example, less than 10 parts by weight relative to 100 parts by weight of the polymer (specifically, the base polymer. For example, an acrylic polymer) contained in the adhesive, and can further be set to less than 5 parts by weight. The content of the above-mentioned adhesion-imparting agent can be less than 1 part by weight (for example, less than 0.5 parts by weight), and can also be less than 0.1 parts by weight (more than 0 parts by weight and less than 0.1 parts by weight). The adhesive can be a substance that does not contain an adhesion-imparting agent.

[0198] (Form of Adhesive Composition)

[0199] Although not particularly limited, the technology disclosed herein can be preferably implemented using a solvent-based adhesive composition. The above-mentioned solvent-based adhesive composition is an adhesive composition in the form of an adhesive-forming component contained in an organic solvent. The solvent-based adhesive composition typically contains a solution polymer of a monomer component, and optionally other additives (such as a multifunctional monomer, a thermal polymerization initiator, etc.). The effect brought about by the technology disclosed herein can be effectively exerted in the form of a solvent-based adhesive (layer). The solvent contained in the solvent-based adhesive composition can be appropriately selected from conventionally known organic solvents. For example, any one solvent selected from the following, or a mixed solvent of two or more, can be used, namely: aromatic compounds such as toluene (typically aromatic hydrocarbons); esters such as ethyl acetate and butyl acetate; aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane; halogenated alkanes such as 1,2-dichloroethane; lower alcohols such as isopropyl alcohol (for example, monohydric alcohols with 1 to 4 carbon atoms); ethers such as tert-butyl methyl ether; ketones such as methyl ethyl ketone; and the like.

[0200] (Adhesive Formation)

[0201] The adhesive disclosed herein can be formed by a method known in the past. After the adhesive composition is imparted (e.g., applied) to a suitable surface, the adhesive can be formed in the form of a layer (adhesive layer) by appropriately implementing a curing treatment. The curing means (e.g., drying, crosslinking, polymerization, cooling, etc.) of the adhesive composition can be only applicable to one, or more than two can be applicable simultaneously or in multiple stages. In a solvent-based adhesive composition, typically, the composition can be dried (preferably further crosslinked) to form an adhesive.

[0202] For example, in the making of the two-sided adhesive sheet without substrate, after the adhesive composition is given to the surface (peel-off surface) with releasability, the method for forming adhesive layer on the surface by making this adhesive composition solidify. In the making of the adhesive sheet with substrate, the method (direct method) can be adopted by directly giving (typically coating) adhesive composition to this substrate and solidifying it to form adhesive layer. In addition, it is also possible to adopt the method (transfer method) by giving adhesive composition to the surface (peel-off surface) with releasability and solidifying it to form adhesive layer on the surface, and this adhesive layer is transferred to substrate. As the above-mentioned peel-off surface, the surface of the release liner, the back side of the substrate through peeling treatment, etc. can be utilized. It should be noted that the adhesive layer disclosed here is typically formed continuously, but is not limited to such form, for example, can also be formed as the adhesive layer of regular or random patterns such as dot-shaped, strip-shaped.

[0203] The adhesive composition can be applied by using a known or commonly used coating machine such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a die coater, a rod coater, an air knife coater, or a spray coater. Alternatively, the adhesive composition can be applied by impregnation, curtain coating, or the like.

[0204] From the viewpoints of promoting the cross-linking reaction and improving the manufacturing efficiency, the drying of the adhesive composition is preferably carried out under heating. The drying temperature is not particularly limited, for example, it can be set to about 40 to 100°C, and is generally preferably set to about 60 to 80°C. For example, the heating temperature of the drying at the above temperature (for example, about 1 to 10 minutes, more specifically about 3 to 7 minutes) is low, and sometimes the volatilization of the solvent is also in progress. In the adhesive composition containing a multifunctional monomer and a thermal polymerization initiator, the reaction of the multifunctional monomer and the deactivation of the thermal polymerization initiator are negligible. In addition, after the adhesive composition is dried, it can be aged for the purpose of adjusting the transfer of components in the adhesive layer, carrying out the cross-linking reaction, and relaxing the strain that may exist in the substrate and the adhesive layer.

[0205] <Adhesive Sheet>

[0206] The thermosetting adhesive disclosed herein can be a form of an adhesive sheet consisting of a layer (adhesive layer) formed by the thermosetting adhesive. The adhesive sheet can be, for example, a form of a non-substrate double-sided adhesive sheet having a first adhesive surface consisting of the surface of one side of the adhesive layer and a second adhesive surface consisting of the surface of the other side of the adhesive layer. Alternatively, the adhesive sheet can also be an adhesive sheet with a substrate having the form of the above-mentioned adhesive layer on one or both sides of a non-peelable substrate (supporting substrate). In the concept of the adhesive sheet mentioned herein, substances referred to as adhesive tapes, adhesive labels, adhesive films, etc. can be included. The adhesive sheet disclosed herein can be in a roll or in a monolithic form. Alternatively, it can be an adhesive sheet further processed into a form of various shapes.

[0207] The structure of the adhesive sheet according to one embodiment is schematically shown in Figure 1 . The adhesive sheet 1 is constructed as a double-sided adhesive sheet without a substrate formed by an adhesive layer 21. The adhesive sheet 1 is used by sticking the first adhesive surface 21A constituted by the surface (first surface) of one side of the adhesive layer 21, and the second adhesive surface 21B constituted by the surface (second surface) of the other side of the adhesive layer 21 to different parts of the adherend. The parts to which the adhesive surfaces 21A and 21B are stuck can be parts of different components or different parts within a single component. For the adhesive sheet 1 before use (i.e., before sticking to the adherend), as Figure 1As shown, it can be a constituent element of the adhesive sheet 50 with a release liner in which the first adhesive surface 21A and the second adhesive surface 21B are protected by release liners 31 and 32, which are at least one side opposite to the adhesive layer 21 and become the release surface. As the release liners 31 and 32, for example, it is preferred to use a release liner that is formed in a manner that the one side becomes the release surface by arranging a release layer based on a release treatment agent on one side of a sheet-like substrate (liner substrate). Alternatively, the release liner 32 can be omitted, and a release liner 31 with two sides becoming the release surface is used, and the release liner 31 is overlapped with the adhesive sheet 1 and rolled into a spiral shape, thereby forming an adhesive sheet with a release liner in a form (roll form) in which the second adhesive surface 21B is abutted against the back side of the release liner 31 and protected.

[0208] (Adhesive layer)

[0209] The thickness of the adhesive layer is not particularly limited. The thickness of the adhesive layer is usually more than 1 μm, can be more than 2 μm, or can be more than 3 μm. There is a tendency that the greater the thickness of the adhesive layer, the higher the adhesion to the adherend. In some preferred embodiments, the thickness of the adhesive layer is more than 5 μm, can be more than 7 μm, or can be more than 9 μm. It is appropriate to set the upper limit of the thickness of the adhesive layer to about 200 μm or less, for example, it can be less than 100 μm (for example, less than 100 μm), or it can be less than 50 μm. By limiting the thickness of the adhesive layer within a specified range, the residual adhesive caused by cohesive failure is prevented from being generated, and there is a tendency to easily obtain easy peelability. In addition, a thin adhesive layer is advantageous in terms of thinning of the adhesive sheet, and there is a tendency to have excellent followability to the adherend. In addition, by adopting a thin adhesive layer, the amount of released gas from the adhesive layer can be reduced. In some preferred embodiments, the thickness of the adhesive layer is 40 μm or less, may be 30 μm or less (eg, less than 30 μm), may be 20 μm or less, or may be 15 μm or less.

[0210] (Base material layer)

[0211] The adhesive sheet disclosed herein may include a substrate layer. As a substrate (layer) supporting (lining) the adhesive layer, various sheet-like substrates can be used. As the above-mentioned substrate, resin film, paper, cloth, rubber sheet, foam sheet, metal foil, their composites, etc. can be used. As examples of resin films, polyolefin films such as polyethylene (PE), polypropylene (PP), and ethylene-propylene copolymers can be cited; polyester films such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN); vinyl chloride resin film; vinyl acetate resin film; polyamide resin film; fluororesin film; cellophane; etc. As other examples of resin films, resin films formed by one or more engineering plastics (which may be super engineering plastics) in polyphenylene sulfide resins, polysulfone resins, polyethersulfone resins, polyetheretherketone resins, polyarylate resins, polyamideimide resins, and polyimide resins can be cited. The use of engineering plastics is preferred from the viewpoint of heat resistance. Examples of paper include Japanese paper, kraft paper, glassine, woodfree paper, synthetic paper, coated paper, etc. Examples of cloth include woven fabrics or nonwoven fabrics obtained by spinning various fibrous materials alone or in a blended manner. Examples of the above-mentioned fibrous materials include cotton, staple fibers, Manila hemp, pulp, rayon, acetate fibers, polyester fibers, polyvinyl alcohol fibers, polyamide fibers, polyolefin fibers, etc. Examples of rubber sheets include natural rubber sheets, butyl rubber sheets, etc. Examples of foam sheets include foamed polyurethane sheets, foamed polychloroprene rubber sheets, etc. Examples of metal foils include aluminum foil, copper foil, etc.

[0212] In some preferred embodiments, a resin film having a specified rigidity (strength) and excellent processability and usability is used as a substrate (layer). Among them, a polyester film is preferably used as the resin film substrate. It should be noted that in this specification, the so-called "resin film" is typically a non-porous film, and typically refers to a resin film that is substantially free of bubbles (voids). Therefore, the above-mentioned resin film is a concept that is different from foam film and non-woven fabric. The density of the resin film that can be used as a substrate can be about 0.85 to 1.50 g / cm 3 (e.g. 0.90 g / cm 3 ~1.20g / cm 3 , typically 0.92 g / cm 3 ~1.05g / cm 3 The resin film may be a single-layer structure or a multi-layer structure with two or more layers (eg, a three-layer structure).

[0213] The substrate layer (e.g., resin film) may be mixed with known additives such as light stabilizers, antioxidants, antistatic agents, colorants (dyes, pigments, etc.), fillers, slip agents, antiblocking agents, etc. as needed. The amount of the additives is not particularly limited and can be appropriately set according to the application, etc.

[0214] The method for producing the resin film is not particularly limited, and for example, a conventionally known general resin film forming method such as extrusion molding, inflation molding, T-die casting, calender roll molding, etc. can be appropriately adopted.

[0215] The substrate layer may be substantially composed of a resin film. Alternatively, the substrate layer may include an auxiliary layer in addition to the resin film. Examples of the auxiliary layer include an optical property adjustment layer (e.g., a coloring layer, an antireflection layer), a printing layer for imparting a desired appearance, a laminating layer, an antistatic layer, a primer layer, a peeling layer, and other surface treatment layers.

[0216] The thickness of the substrate layer is not particularly limited, and can be appropriately selected according to the purpose, and can generally be 1 to 500 μm. From the viewpoints of processability, usability, operability, etc., it is appropriate that the thickness of the substrate layer is 2 μm or more (e.g., 3 μm or more, typically 5 μm or more), can be about 7 μm or more, or can be 10 μm or more. In addition, it is appropriate that the thickness of the substrate layer is about 200 μm or less, and from the viewpoint of lightweight and thin thickness, it is preferably about 100 μm or less, more preferably about 50 μm or less, can be 30 μm or less, can be 20 μm or less, or can be 15 μm or less. When the thickness of the substrate layer becomes smaller, there is a tendency to improve the softness of the adhesive sheet and the followability of the surface shape of the adherend.

[0217] The adhesive layer side surface of the substrate layer can be subjected to corona treatment, plasma treatment, ultraviolet irradiation treatment, acid treatment, alkali treatment, coating of primer (primer) and other previously known surface treatments as needed. Such surface treatment can be used to improve the adhesion between the substrate layer and the adhesive layer, in other words, it can be used to improve the anchoring of the adhesive layer to the substrate layer. The composition of the primer is not particularly limited and can be appropriately selected from known substances. The thickness of the primer layer is not particularly limited, for example, about 0.01 μm to 1 μm is appropriate, preferably about 0.1 μm to 1 μm. In addition, the back of the substrate layer can be subjected to the above-mentioned various surface treatments, antistatic treatment and other surface treatments.

[0218] (Total Thickness)

[0219] The total thickness of the adhesive sheet disclosed herein (which may include an adhesive layer and a substrate layer, but does not contain a release liner) is not particularly limited, and it is appropriate to set it in the range of about 5 to 1000 μm. From the perspectives of adhesive properties and usability, the total thickness of the adhesive sheet can be more than 10 μm, more than 15 μm, or more than 20 μm. In addition, from the perspective of lightweight and thin thickness, in some embodiments, the total thickness of the adhesive sheet is less than 500 μm, or less than 300 μm. In some preferred embodiments, the total thickness of the adhesive sheet is less than 100 μm (for example, less than 100 μm), more preferably less than 50 μm, or less than 30 μm. Reducing the thickness of the adhesive sheet is also advantageous in terms of filmization, miniaturization, lightweighting, and resource saving.

[0220] <Release liner>

[0221] The release liner used for the adhesive sheet disclosed herein is not particularly limited, and for example, a release liner having a release treatment on the surface of a liner substrate such as a resin film or paper, a release liner formed of a low-adhesive material such as a fluorine-based polymer (polytetrafluoroethylene, etc.) or a polyolefin-based resin (polyethylene, polypropylene, etc.) can be used. In the above-mentioned release treatment, for example, a release treatment agent such as a silicone-based or long-chain alkyl-based release agent can be used. In some embodiments, a release-treated resin film can be preferably used as the release liner.

[0222] <Joint body>

[0223] The thermosetting adhesive disclosed herein can be used for a joined body that is arranged between two members (adherends) to join the two members. In the above-mentioned joined body, the thermosetting adhesive disclosed herein is used for a joining portion that joins the above-mentioned two members.

[0224] The conjugate disclosed herein may be, for example, Figure 2 The joint body 100 has a cross-sectional structure schematically shown in FIG. The joint body 100 includes a first member 71, a second member 72, and a joint portion 80, and the joint portion 80 is arranged between the first member 71 and the second member 72. The joint body 100 has a structure of a laminated body including the first member 71, the joint portion 80, and the second member 72 in this order. Figure 2 In the embodiment of the present invention, the first member 71 and the second member 72 are in the form of a sheet or a plate, and the joint 80 is a layered body. In addition, in this embodiment, both the first member 71 and the second member 72 are rigid bodies. The joint 80 is composed of a thermosetting adhesive 90, and joins the first member 71 and the second member 72. In other words, the first member 71 and the second member 72 are joined via the joint 80 containing the thermosetting adhesive 90. Figure 2In the embodiment, the joint portion 80 is in the form of a layer (thermosetting adhesive layer) formed by a thermosetting adhesive 90. In this embodiment, with respect to the joint body 100, a substrate-free adhesive sheet formed by a thermosetting adhesive layer is used as the joint portion 80, and the adhesive surface (first adhesive surface) on one side of the adhesive sheet (thermosetting adhesive layer) which is a surface 80A on one side of the joint portion 80 is bonded to the first component 71 which is an adherend, and the adhesive surface (second adhesive surface, opposite to the first adhesive surface) on the other side of the adhesive sheet (thermosetting adhesive layer) which is a surface 80B on the other side of the joint portion 80 is bonded to the second component 72 which is an adherend.

[0225] It should be noted that, in the above-mentioned embodiment, the first member, the second member and the joint part constituting the joint body are all configured in a layered, sheet-like or plate-like shape, and the joint body has the form of a stacked structure (stacked body), and the shapes of the first member, the second member and the joint part may not be layered, sheet-like or plate-like, but may be configured in various shapes. For example, the first member and the second member may have a surface in contact with the joint part, and may have various three-dimensional member shapes such as complex shapes and curved surface shapes based on the purpose of use and use. The joint part may also have various shapes according to the surface shapes of the first member and the second member.

[0226] In addition, in this specification, the term "component" in the first component and the second component is used in the meaning of the constituent element of the joint body, and is not particularly limited except for this meaning. For example, the first component and the second component can each be an independent article or component, or can be components that constitute different articles.

[0227] In addition, as the joint part comprising thermosetting adhesive, as in the above-mentioned embodiment, a non-substrate adhesive sheet formed only by an adhesive layer can be used, or a two-sided adhesive sheet with a substrate can also be used. When the non-substrate adhesive sheet is used for the joint part, the joint part in the joint body can be an adhesive or a layer (adhesive layer) formed by an adhesive. In addition, when the two-sided adhesive sheet with a substrate is used for the joint part, the joint part in the joint body can be a composition having a laminated structure having the first adhesive layer, a substrate layer and the second adhesive layer in sequence. In this way, the thermosetting adhesive disclosed herein is contained in at least one of the first adhesive layer and the second adhesive layer.

[0228] In addition, the bonded body may optionally include other members and components in addition to the first and second members. For example, when the first and second members are parts of a product such as an electronic device, the bonded body may be a structure composed of a plurality of members and components.

[0229] <How to disassemble a bonded body>

[0230] According to the present specification, a method for disassembling the joint disclosed herein is provided. The above-mentioned disassembly method includes: subjecting the above-mentioned joint to a heat treatment at a temperature higher than 150°C to separate the first component from the second component. The joint contains a thermosetting adhesive disclosed herein, and the thermosetting adhesive has a heat-peelable property such that the peel strength after heating of the glass plate measured after heating at 180°C for 30 minutes is less than 1.0N / 20mm. The above-mentioned thermosetting adhesive is used for the joint portion, and by performing a heating treatment exceeding 150°C, the joint state between the first component and the second component can be easily released. For example, even in the case where the first component and the second component are both rigid bodies and the deformation of the adherends cannot be used for peeling, since the thermosetting adhesive contained in the joint portion has a heat-peelable property, the joint can be disassembled by short-term high-temperature heating.

[0231] The heat treatment of the bonded body is to heat at least the bonded portion, and the heating can be implemented via the first component and the second component. The heating means is not particularly limited, and means such as putting into a high-temperature room such as an oven and sending hot air can be used. The temperature of the heating treatment can be above 160°C, or above 170°C. The upper limit of the heating treatment temperature can vary depending on the purpose of the heating treatment, the heat resistance of the adherend, etc., and is generally below 250°C, and can be below 230°C or below 200°C. The heating treatment time can be more than 3 minutes, more than 5 minutes, more than 10 minutes, or more than 20 minutes. In addition, from the perspective of the efficiency of the heating process, the heating treatment time can be within 1 hour or within 30 minutes. The thermosetting adhesive disclosed herein is thermally cured by the above-mentioned short-time high-temperature heating treatment, and can show easy peeling by heating. In addition, in some embodiments, the heating treatment time can be more than 10 minutes, more than 30 minutes, more than 60 minutes, more than 1 hour, more than 3 hours, more than 4 hours, or more than 5 hours. For the thermosetting adhesive disclosed herein, the adhesive is thermally cured by the above-mentioned high-temperature heating treatment, the peeling force is reduced, or the increase in the peeling force is suppressed, and even if the heating state continues for a long time, the increase in the peeling force (heavy peeling) will not occur or be suppressed. Therefore, the heating easy peelability can be maintained even after a long period of heating treatment. The upper limit of the heating treatment time is not particularly limited, but from the viewpoint of the efficiency of the heating process, it can be within 10 hours, within 5 hours, or within 3 hours.

[0232] In addition, some preferred embodiments involve thermosetting adhesives (which may be in the form of adhesive sheets comprising thermosetting adhesives) that have desired adhesive properties even when stored for a specified period before being attached to an adherend. The above-mentioned thermosetting adhesive has good storage stability, so even when exposed to temperatures above 40°C (e.g., above 40°C and below 100°C), further exposed to temperatures above 50°C or above 60°C during storage, the desired adhesive properties and heat resistance and easy peelability can be maintained. Even in an environment below 40°C, such as long-term storage for more than 30 days, more than 100 days, or even half a year or more than a year, changes will occur in the adhesive properties originally designed. In particular, regarding adhesives with heat-peelable properties, there is a risk that the heat-polymerization initiator will decompose due to long-term storage, thereby impairing the desired heat-peelable properties. However, the above-mentioned thermosetting adhesive has heat-peelable properties and good storage stability. Therefore, regardless of long-term storage, temperature conditions during storage, etc., it can exhibit heat-resistant peelable properties after storage and has high utilization value.

[0233] <First member and second member>

[0234] The materials of the first component and the second component constituting the joint body are not particularly limited, and various materials exemplified as the adherend materials described later can be used. For example, a material consisting of one or more of glass, metal material, ceramic material and resin material can be used. In the technology disclosed herein, glass, metal material and ceramic material can be used as the first component and the second component. These materials have a prescribed heat resistance, and therefore the heating easy peeling technology disclosed herein can be applied. In addition, the above-mentioned materials are typical examples of rigid materials. When the first component and the second component are both rigid bodies, the deformation of the components cannot be utilized to separate the components from the joint portion, but according to the technology disclosed herein, by carrying out a prescribed heating of the heating easy peeling type adhesive contained in the joint portion, the joint between the rigid bodies can be easily released. The materials of the first component and the second component can be the same, or they can also be different.

[0235] It should be noted that the so-called "rigid body" refers to an object with rigidity and size that is substantially not deformed by human power. In this specification, it refers to an object that cannot be deformed to a level that improves disassembly performance by human power (normal adult male standard) from the state of the joint when the joint is disassembled. Although not particularly limited, the so-called "rigid body" in this specification refers to an object that satisfies the tensile elastic modulus of 1×10 10 Pa or more; and bending rigidity of 0.01Pa·m 3 An object comprising at least one of the above;

[0236] The tensile modulus is measured in accordance with JIS K 7161. More specifically, the tensile modulus is measured by the following method.

[0237] [Tensile test]

[0238] The object to be measured was cut into a strip shape with a width of 10 mm to prepare a test piece. The test piece was stretched under the following conditions in accordance with JIS K7161 to obtain a stress-strain curve.

[0239] (Stretching conditions)

[0240] Measurement temperature: 25℃

[0241] Stretching speed: 300mm / min

[0242] Distance between chucks: 50mm

[0243] As the tensile testing machine, a universal tensile compression testing machine (device name: "tensile compression testing machine, TCM-1kNB", manufactured by Minebea Co., Ltd.) or its equivalent can be used.

[0244] The tensile elastic modulus was obtained by linear regression of the above stress-strain curve.

[0245] In addition, when the thickness of the material is h [m], the Poisson's ratio of the material is ν, and the tensile elastic modulus is E [Pa], the bending rigidity value D [Pa·m 3 ] is the value obtained by the following formula:

[0246] D=Eh 3 / 12(1-ν 2 ).

[0247] The thickness of the glass (e.g., glass plate), metal material (e.g., metal plate), and ceramic material (e.g., ceramic plate) that can be used as the first component and / or the second component is not particularly limited, and can be, for example, about 0.1 mm or more, or about 0.5 mm or more. Glass, metal material, and ceramic material having a thickness within the above range can have the properties of a rigid body, and therefore the advantages of the technology disclosed herein are prominent. The maximum thickness of the above-mentioned glass, metal material, and ceramic material is not particularly limited, and can be about 30 cm or less, about 10 cm or less, about 1 cm or less, about 5 mm or less, or about 2 mm or less.

[0248] In addition, as a resin material (typically a plastic material) that can be used as the first member and / or the second member, a material that satisfies a tensile elastic modulus of 1×10 10 Pa or more; and bending rigidity of 0.01Pa·m3 Above; at least one of, and the heat-resistant temperature (continuous heat-resistant temperature) is 150°C or above (for example, more than 150°C, more than 160°C, more than 170°C, more than 180°C or more than 180°C). The above-mentioned heat-resistant temperature (continuous heat-resistant temperature) can be obtained based on JIS K7226. As examples of the above-mentioned resin materials, polyester resins, acrylic resins, ABS resins, polycarbonate resins, polystyrene resins, polyimide resins, etc. can be cited. Although not particularly limited, the thickness of the above-mentioned resin material is, for example, about 1 mm or more, about 2 mm or more, about 3 mm or more, about 5 mm or more, or about 1 cm or more. The resin material having a thickness in the above-mentioned range may have the property of being a rigid body, so the advantages of applying the technology disclosed herein are outstanding. The maximum thickness of the above-mentioned resin material is not particularly limited, and may be about 30 cm or less, about 10 cm or less, or about 1 cm or less.

[0249] <Application>

[0250] The thermosetting adhesive disclosed herein has the property of being easily peelable by heating, and therefore can be used in various applications in which the adhesive is used to be bonded to an adherend and removed from the adherend after the bonding purpose is completed. Although not particularly limited, in the case of applications such as bonding to light-opaque adherends or adherends with low conductivity, which are not suitable for ultraviolet irradiation peeling adhesives and electrical peeling adhesives, the thermosetting adhesive disclosed herein can be ideally applied to adherends with a specified heat resistance. In addition, the thermosetting adhesive disclosed herein can easily release the bonding between rigid bodies, and therefore is particularly suitable for applications using rigid bodies as adherends. For example, it can be used as a thermosetting adhesive and adhesive sheet for masking, temporary fixing, or protection.

[0251] In addition, the thermosetting adhesive and adhesive sheet disclosed herein, for example, can also be preferably used as a process material fixed to an adherend and peeled off in the manufacturing process of electronic equipment and electronic components. In addition, as suitable uses of the thermosetting adhesive and adhesive sheet disclosed herein, semiconductor element manufacturing purposes can be cited. For example, in semiconductor wafer processing (typically silicon wafer processing), it can be preferably used as a wafer fixing sheet for fixing the wafer to a fixed plate. In addition, the thermosetting adhesive and adhesive sheet disclosed herein can also be preferably used as a protective sheet for protecting the wafer in the above-mentioned wafer processing.

[0252] In addition, the thermosetting adhesive and adhesive sheet disclosed herein can also be applied to optical applications. More specifically, for example, as an optical adhesive sheet for bonding optical components (optical component bonding), the manufacturing application of products (optical products) using the above-mentioned optical components, etc., the adhesive sheet disclosed herein can be used. It should be noted that the above-mentioned optical component refers to a component having optical properties (for example, polarization, light refraction, light scattering, light reflection, light transmittance, light absorption, light diffraction, optical rotation, visual recognition, etc.). As the above-mentioned optical component, it is a component with optical properties, which is not particularly limited. For example, components constituting devices (optical devices) such as display devices (image display devices) and input devices or components that can be used for these devices can be cited. As the above-mentioned display device, for example, a liquid crystal display device, an organic EL (electroluminescence) display device, a PDP (plasma display panel), an electronic paper, etc. can be cited. In addition, as the above-mentioned input device, a touch panel, etc. can be cited.

[0253] The thermosetting adhesive and adhesive sheet disclosed herein have good adhesion and can be removed by peeling off by short-term high-temperature heating. Therefore, they can be preferably used as adhesives and adhesive sheets for electronic devices (suitably portable electronic devices) that require adhesion reliability during use and require smooth removal during repair, replacement, inspection, recycling, etc. of the constituent components. For example, in mobile phones, smart phones, tablet personal computers, notebook computers, various wearable devices (for example, wrist-worn types worn on the wrist like a watch, modular types worn on a part of the body by clips, straps, etc., glasses-type (monocular type, binocular type. Also including head-worn types), glasses-type, clothing types installed on shirts or socks, hats, etc., such as in the form of accessories, earring types worn on the ears like headphones, etc.), digital cameras, digital video cameras, audio equipment (portable music players, IC recorders, etc.), calculators (desktop electronic calculators, etc.), portable game consoles, electronic dictionaries, electronic recorders, etc. In portable electronic devices such as notebooks, e-books, in-vehicle information devices, portable radios, portable televisions, portable printers, portable scanners, and portable modems, it is ideally suitable for fixing the protective panel (lens) that protects the display, fixing the key module components, fixing the antenna module, fixing the flange sheet, fixing the decorative panel, fixing the battery, fixing various other components (circuit substrates, various panel components, buttons, lighting equipment components, internal camera components, heat dissipation materials, graphite sheets), fixing logos (design text), various designs and other display objects (including various logos), etc. It should be noted that in this manual, the so-called "portable" is not enough to be able to be carried, but refers to the portability that an individual (a standard adult) can carry and move relatively easily.

[0254] The thermosetting adhesive and adhesive sheet disclosed herein are suitable as adhesives and adhesive sheets used for the purpose of fixing batteries (including primary batteries and secondary batteries, such as polymer batteries) to the main body of the electronic device in an electronic device (typically a portable electronic device). Usually, the battery is mostly arranged in a position that needs to be removed when the components (including batteries) of the electronic device are repaired, replaced, inspected, etc. Therefore, the adhesive and adhesive sheet used to fix the battery need to be removed frequently. By applying the above-mentioned adhesive or adhesive sheet in this use, the function of fixing the battery can be well exerted, and when the battery is removed after the use period ends, the removal can be easily performed by high-temperature heating. According to the adhesive and adhesive sheet disclosed herein, the above-mentioned disassembly method can be used to suppress the deformation of the battery and the adhesive and adhesive sheet can be well removed.

[0255] In addition, the thermosetting adhesive and adhesive sheet disclosed herein are suitable for the purposes of bonding brittle materials (typically hard and brittle materials) such as glass. For example, in the purposes of fixing 2 adherends and in the mode in which at least one of the adherends is formed by brittle materials such as glass materials, the adhesive and adhesive sheet disclosed herein can be preferably used. Specifically, the fixed purposes of glass materials such as windshields and window glasses of vehicles, the window glasses composed of multilayer glass plates, antibacterial glass, etc., which make glass materials bonded to each other, can be cited. In addition, the fixing of glass parts (lenses, etc.) to the frame with glass plates, the fixing of panels, and the bonding of glass plates to each other are also suitable purposes of the adhesive and adhesive sheet disclosed herein.

[0256] In each of the above-mentioned uses, the thermosetting adhesive and the adhesive sheet can be exposed to heating exceeding 150°C (exceeding 150°C and about 250°C or less, for example, 160°C or more, and further 170°C or more) in the state of being attached to the adherend. The thermosetting adhesive and the adhesive sheet disclosed herein can also be a material having heat-resistant and easy-to-peel properties, and therefore can also be preferably used for uses exposed to the above-mentioned heating. For example, in the manufacture of semiconductor elements, since they are exposed to heating during the processing steps, etc., it is ideal to use an adhesive sheet having heat-resistant and easy-to-peel properties.

[0257] In addition, the release gas of the thermosetting adhesive and adhesive sheet involved in some preferred embodiments is reduced, so it can be ideally used for various purposes where the release gas is not expected. For example, in the use of pressure difference for temporary fixation of materials, the use of adhesive sheets, and the use of processing adherends under vacuum, the adhesive sheet is used in a vacuum or reduced pressure environment. In these uses, if the amount of released gas from the adhesive or adhesive sheet is large, the vacuum degree is reduced, which may become the cause of undesirable conditions. The above-mentioned thermosetting adhesive and adhesive sheet can be used for various uses including the above-mentioned uses where the release gas is not expected.

[0258] The type of material (adherend material) disclosed herein for pasting is not particularly limited. The adhesive sheet disclosed herein can be used for fixing and protecting various components and materials. As examples of adherend materials, for example, it can be: glasses such as alkaline glass and alkali-free glass; metal materials such as stainless steel (SUS) and aluminum; ceramic materials such as alumina and silica; resin materials such as polyester resins such as PET, acrylic resins, ABS resins, polycarbonate resins, polystyrene resins, and transparent polyimide resins; and so on. As suitable examples of adherend materials, for example, glass materials such as alkaline glass, semiconductor chips, etc. can be cited. The above-mentioned glass material can be, for example, a glass plate having a surface with a transparent conductive film (such as ITO (indium tin oxide) film) and FPC (flexible circuit board) that can be used for tablet personal computers, mobile phones, organic LEDs (light emitting diodes), etc.

[0259] The matters disclosed in this specification include the following.

[0260] [1] A joint body comprising a first member, a second member, and a joint portion, the joint portion being arranged between the first member and the second member and joining the first member and the second member, wherein:

[0261] The aforementioned joint portion comprises a thermosetting adhesive,

[0262] The post-heating peel strength of the thermosetting adhesive relative to a glass plate measured after heating at 180° C. for 30 minutes is 1.0 N / 20 mm or less.

[0263] [2] The joined body according to [1] above, wherein the first member and the second member are both rigid bodies.

[0264] [3] The bonded body according to [1] or [2] above, wherein the material of the first member and the material of the second member are the same as or different from each other and are each composed of glass, a metal material or a ceramic material.

[0265] [4] The joined body according to any one of [1] to [3] above, wherein the thermosetting adhesive has a post-heating peel strength relative to a glass plate of 1.0 N / 20 mm or less measured after heating at 180° C. for 1 hour.

[0266] [5] The joined body according to any one of [1] to [4] above, wherein the joined portion is formed of the thermosetting adhesive.

[0267] [6] The joined body according to any one of [1] to [5] above, wherein the thermosetting adhesive contains a thermal polymerization initiator.

[0268] [7] The joined body according to any one of [1] to [6] above, wherein the thermosetting adhesive comprises a polymer and a polyfunctional monomer.

[0269] [8] A thermosetting adhesive for use in the joined body described in any one of [1] to [7] above, wherein:

[0270] The post-heating peel strength of the thermosetting adhesive relative to a glass plate measured after heating at 180° C. for 30 minutes was 1.0 N / 20 mm or less.

[0271] [9] A disassembly method, which is a method for disassembling a joined body according to any one of [1] to [7] above, the disassembly method comprising:

[0272] A step of subjecting the bonded body to a heat treatment at a temperature higher than 150° C. to separate the first member from the second member.

[0273] Example

[0274] Hereinafter, some embodiments of the present invention will be described, but the present invention is not intended to be limited to the contents shown in these embodiments. It should be noted that, unless otherwise specified, in the following description, "parts" and "%" are based on weight.

[0275] <Example 1>

[0276] (Preparation of Adhesive Composition)

[0277] Into a reaction container equipped with a cooling tube, a nitrogen introduction tube, a thermometer and a stirring device, 85 parts of methoxyethyl acrylate (MEA), 10 parts of N-vinyl-2-pyrrolidone (NVP), 5 parts of 4-hydroxybutyl acrylate (4HBA) and 0.5 parts of acrylic acid (AA) as monomer components, 300 parts of ethyl acetate as a polymerization solvent, and 0.2 parts of 2,2'-azobisisobutyronitrile (AIBN) as a thermal polymerization initiator were added, and a polymerization reaction (solution polymerization) was carried out at 61° C. for 6 hours under a nitrogen atmosphere, thereby obtaining a solution containing an acrylic polymer A.

[0278] To the toluene solution of the acrylic polymer A, 30 parts of dipentaerythritol hexaacrylate (DPHA) as a multifunctional monomer, 3 parts of an isocyanate crosslinking agent (manufactured by Mitsui Chemicals, product name "Takenate D-101E"), and 0.5 parts of benzoyl peroxide (manufactured by NOF Corporation, product name "NYPER BMT 40SV", 10-hour half-life temperature: 73°C) as a thermal polymerization initiator were added relative to 100 parts of the acrylic polymer A, and the mixture was uniformly mixed to prepare the solvent-based adhesive composition involved in this example.

[0279] (Production of Adhesive Sheet)

[0280] The adhesive composition obtained in the above manner was applied to the release surface of a commercially available PET release liner and dried at 80°C for 5 minutes to form an adhesive layer (a layer formed of a thermosetting adhesive) with a thickness of 40 μm. The release surface of another commercially available PET release liner was attached to the adhesive layer. Thus, a substrate-free double-sided adhesive sheet with a thickness of 40 μm, the two sides of which were protected by the above two PET release liners, was obtained.

[0281] <Examples 2 to 9 and Comparative Examples 1 and 2>

[0282] The amount of the multifunctional monomer, the type and amount of the thermal polymerization initiator were changed as shown in Table 1. The adhesive compositions involved in each example were prepared by the same method as in Example 1, and the substrate-free double-sided adhesive sheets involved in each example were prepared using the obtained adhesive compositions in the same manner as in Example 1. It should be noted that in Table 2, the azo polymerization initiator refers to the product name "VAm-110" (2,2'-azobis(N-butyl-2-methylpropionamide), 10-hour half-life temperature: 110°C) manufactured by FUJIFILM Wako Pure Chemical Corporation.

[0283] <Example 10>

[0284] Into a reaction vessel equipped with a cooling tube, a nitrogen introduction tube, a thermometer and a stirring device, 100 parts of monomer components including 80 mol% of 2-ethylhexyl acrylate (2EHA) and 20 mol% of hydroxyethyl acrylate (HEA), and 65 parts of toluene as a polymerization solvent, 0.2 parts of benzoyl peroxide as a thermal polymerization initiator were added, and polymerization reaction (solution polymerization) was carried out at 61° C. for 6 hours under a nitrogen atmosphere to obtain a solution containing an acrylic polymer B. Methacryloxyethyl isocyanate (MOI) was added to the solution of the acrylic polymer b in an amount of 16 mol% relative to 20 mol% of HEA, and an addition reaction treatment was carried out at 50° C. for 48 hours in an air flow to obtain an acrylic polymer B having a methacryloyl group at the end of the side chain.

[0285] In the toluene solution of the acrylic polymer B, 1 part of the above-mentioned isocyanate crosslinking agent and 3 parts of benzoyl peroxide (manufactured by NOF Corporation, product name "NYPER BMT 40SV", 10-hour half-life temperature: 73°C) as a thermal polymerization initiator are added relative to 100 parts of the acrylic polymer B, and the mixture is evenly mixed to prepare the solvent-based adhesive composition involved in this example.

[0286] The obtained PSA composition was used in the same manner as in Example 1 to produce a substrate-free double-sided PSA sheet according to this example.

[0287] <Example 11 and Comparative Examples 3 to 5>

[0288] The type and amount of the thermal polymerization initiator were changed as shown in Table 1. Except for this, the adhesive composition involved in each example was prepared by basically the same method as in Example 10, and the obtained adhesive composition was used to make the substrate-free double-sided adhesive sheet involved in each example in the same manner as in Example 10.

[0289] <Evaluation>

[0290] (Initial peel strength F0)

[0291] The adhesive composition involved in each example was applied on the release surface of a commercially available PET release liner, and dried at 80°C for 5 minutes to form an adhesive layer with a thickness of 10 μm. A PET film with a thickness of 12 μm was attached to the adhesive layer to make an adhesive sheet (a single-sided adhesive sheet with a substrate). The adhesive sheet obtained in the above manner was cut into a size of 20 mm in width and 100 mm in length, and a 2 kg roller was reciprocated once under an environment of 23°C and 50% RH to crimp the adhesive surface of the adhesive sheet and attach it to an alkaline glass plate (made by Matsunami Glass Industry Co., Ltd., with a thickness of 1.35 mm, and a blue plate edge grinding product) as an adherend. Under the same environment, the alkaline glass plate with the above-mentioned adhesive sheet was left to stand for 6 hours and used as an evaluation sample. The above-mentioned evaluation sample is placed in a tensile testing machine under an environment of 23°C and 50% RH, and the peel strength (initial peel strength) F0 [N / 20mm width] when the adhesive sheet is peeled off from the adherend at a peeling angle of 180 degrees and a speed of 300mm / min is measured. The obtained value is set as the initial peel strength F0 of the thermosetting adhesive on glass. As a tensile testing machine, the product name "EZ-S 500N" manufactured by Shimadzu or its equivalent can be used. In addition, when the evaluation object is a double-sided adhesive sheet, the non-measurement surface can be lined with a PET film to implement the measurement.

[0292] (Peel strength after heating F1)

[0293] Using the adhesive composition involved in each example, an adhesive sheet is prepared by the method described in the above-mentioned determination of the initial peel strength F0, and an evaluation sample is prepared. The obtained evaluation sample is heat-treated in an oven at 180°C for 30 minutes, taken out of the oven, and allowed to stand for 30 minutes under an environment of 23°C and 50% RH. Then, the above-mentioned evaluation sample is set in a tensile testing machine under the same environment, and the peel strength (peel strength after heating) F1 [N / 20mm width] when the adhesive sheet is peeled off from the adherend at a peeling angle of 180 degrees and a speed of 300mm / min is measured. The obtained value is set as the peel strength F1 of the thermosetting adhesive on glass after heating. Regarding the adherend, the tensile testing machine, and other matters, it is the same as the determination of the initial peel strength F0.

[0294] (Peel strength after heating F2)

[0295] Using the adhesive composition involved in each example, an adhesive sheet is prepared by the method described in the above-mentioned initial peel strength F0 measurement, and an evaluation sample is prepared. The obtained evaluation sample is heated in an oven at 180°C for 1 hour, taken out of the oven, and allowed to stand for 30 minutes under an environment of 23°C and 50% RH. Then, the above-mentioned evaluation sample is set in a tensile testing machine under the same environment, and the peel strength (peel strength after heating) F2 [N / 20mm width] when the adhesive sheet is peeled off from the adherend at a peeling angle of 180 degrees and a speed of 300mm / min is measured. The obtained value is set as the peel strength F2 of the thermosetting adhesive on glass after heating. Regarding the adherend, the tensile testing machine, and other matters, it is the same as the measurement of the initial peel strength F0.

[0296] (Disassembly of the joint body)

[0297] The two-sided adhesive sheet involved in each example is cut into a size of 165mm×65mm, so that the first adhesive surface exposed by peeling off the release liner is bonded to the alkaline glass plate A (made by Songlang Glass Industry Co., Ltd., with a thickness of 1.35mm and a blue plate edge grinding product) as the first component, and the second adhesive surface exposed by peeling off the release liner is bonded to the alkaline glass plate B (made by Songlang Glass Industry Co., Ltd., with a thickness of 1.35mm and a blue plate edge grinding product) as the second component, and the obtained object is put into an autoclave, and treated for 15 minutes (autoclave treatment) under the conditions of 50°C and 5 atmospheres, and after being taken out from the autoclave, it is left to stand at room temperature and pressure (23°C, 1 atmosphere) for 30 minutes. Thus, a bonded body of a laminated structure formed by an alkaline glass plate A / adhesive layer / alkaline glass plate B is obtained as an evaluation sample. In this evaluation sample, alkaline glass plates A and B are bonded with an adhesive layer with a bonding area of ​​165mm×65mm. It should be noted that the tensile elastic modulus of the alkaline glass plates A and B is 7×10 10Pa, bending rigidity is about 14Pa·m 3 (Poisson's ratio 0.23).

[0298] The obtained bonded body was heated in an oven at 180°C for 30 minutes, taken out of the oven, and allowed to stand for 30 minutes in an environment of 23°C and 50% RH, and then the bonded body was disassembled by hand (all evaluations of adult women were performed by the same person). Specifically, a ruler (or a metal plate) was inserted into the interlayer part of the end of the evaluation sample to about 10 mm, and then a force was applied in the vertical direction (thickness direction of the evaluation sample) to attempt disassembly.

[0299] The case where the bonded body could be disassembled was evaluated as “possible”, and the case where the bonded body could not be disassembled was evaluated as “impossible”.

[0300] Table 1 shows the summary and evaluation results of each example.

[0301] [Table 1]

[0302] As shown in Table 1, from the comparison results of Examples 1 to 11 and Comparative Examples 1 to 5, it can be seen that by using a thermosetting adhesive having a peel strength F1 of 1.0 N / 20 mm or less after 30 minutes of heat treatment at 180°C, it is possible to disassemble a bonded body formed by bonding rigid bodies to each other.

[0303] Although the specific examples of the present invention have been described in detail above, these are merely examples and do not limit the claims. The technology described in the claims includes examples obtained by variously modifying and changing the specific examples described above.

[0304] Description of Reference Numerals

[0305] 1 Adhesive sheet

[0306] 21 Adhesive layer

[0307] 21A 1st adhesive surface

[0308] 21B Second adhesive surface

[0309] 31, 32 Release liner

[0310] 50 Adhesive sheet with release liner

[0311] 71 Component 1

[0312] 72 Component 2

[0313] 80 joint

[0314] 90 Thermosetting Adhesive

[0315] 100 joint body

Claims

1. A joint body comprising a first member, a second member, and a joint portion, wherein the joint portion is arranged between the first member and the second member and joins the first member and the second member, wherein: The joining portion comprises a thermosetting adhesive, The thermosetting adhesive has a post-heating peel strength to a glass plate measured after heating at 180° C. for 30 minutes of 1.0 N / 20 mm or less.

2. The conjugate according to claim 1, wherein The first member and the second member are both rigid bodies.

3. The conjugate according to claim 2, wherein: The material of the first member is the same as or different from that of the second member, and each of them is made of glass, metal material or ceramic material.

4. The conjugate according to any one of claims 1 to 3, wherein The thermosetting adhesive has a post-heating peel strength to a glass plate measured after heating at 180° C. for 1 hour of 1.0 N / 20 mm or less.

5. The conjugate according to any one of claims 1 to 3, wherein The joining portion is formed by the thermosetting adhesive.

6. The conjugate according to any one of claims 1 to 3, wherein The thermosetting adhesive contains a thermal polymerization initiator.

7. The conjugate according to any one of claims 1 to 3, wherein The thermosetting binder includes a polymer and a multifunctional monomer.

8. A thermosetting adhesive for use in the joined body according to any one of claims 1 to 3, wherein: The thermosetting adhesive has a post-heating peel strength to a glass plate measured after heating at 180° C. for 30 minutes of 1.0 N / 20 mm or less.

9. A disassembly method, which is a method for disassembling a joined body according to any one of claims 1 to 3, the disassembly method comprising: The step of heat-treating the bonded body at a temperature higher than 150° C. to separate the first member from the second member.

Citation Information

Patent Citations

  • Sheet for fixing semiconductor wafer and chip pick-up method

    JP1998209087A

  • Wafer processing method

    JP2015029105A

  • Thermosetting adhesive composition for adhesive sheet for protecting chemical, adhesive for adhesive sheet for protecting chemical by crosslinking same, adhesive sheet for protecting chemical and application method of adhesive sheet for protecting chemical

    JP2016204617A

  • Double faced adhesive tape, and stacking body of thin film component and supporting component

    JP2019056101A

  • Game machine

    JP2022120903A